Lithium-ion cells with high-performance electrolytes and silicon dioxide active materials that achieve extremely long cycle life performance.

JP7933852B2Active Publication Date: 2026-10-13IONBLOX INC
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2024229830
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-08-30
Filing Date
2024-12-26
Publication Date
2026-10-13
Estimated Expiration
2040-06-19

AI Technical Summary

Benefits of technology

をもたらすものである。本出願人は、不可逆容量損失の補充に対応するよりも多い量で提供された相補的リチウムにより、サイクリングをさらに安定化させ得ることを発見した。リチウムリッチ+マンガンリッチ酸化ニッケルマンガンコバルト、正極活性材料に関して、このサイクリング安定化は、参照によって本明細書に組み込まれる、「Lithium Ion Batteries With Supplemental Lithium」という名称の、Amiruddinらへの米国特許第9,166,222号明細書(以下、‘222特許)に記載されている。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007933852000007
    Figure 0007933852000007
  • Figure 0007933852000008
    Figure 0007933852000008
  • Figure 0007933852000009
    Figure 0007933852000009
Patent Text Reader

Abstract

To provide a lithium-ion cell that achieves good cycling capability.SOLUTION: A lithium-ion cell includes a negative electrode having an active material having a silicon oxide-based material and graphite, a positive electrode, a separator, an electrolyte having a lithium salt and a non-aqueous solvent, and a container. The electrolyte provides unprecedented cycling performance for a battery having a negative electrode having a substantial amount of silicon-based active material to achieve high specific capacity. The electrolyte also uses a significant amount of fluoroethylene carbonate solvent, and appropriately selects other solvent components such as dimethyl carbonate, methyl ethyl carbonate, and diethyl carbonate to exclude other unstable components and provide stability.SELECTED DRAWING: Figure 24
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] Cross-reference of related applications This application claims priority to U.S. Patent Application Publication No. 16 / 556,670, filed with Dong et al., entitled “Lithium Ion Cells With High Performance Electrolyte And Silicon Oxide Active Materials Achieving Very Long Cycle Life Performance,” and to U.S. Provisional Patent Application No. 62 / 866,978, filed with Dong et al. on June 26, 2019, entitled “Lithium Ion Cells With High Performance Electrolyte And Silicon Oxide Active Materials Achieving Very Long Cycle Life Performance,” both of which are incorporated herein by reference.

[0002] Federal government-funded research and development This invention was implemented with government support under U.S. Government funding agreement number DE-EE0006250, based on the United States Advanced Battery Consortium Program Number 18-2216-ABC, as granted by the U.S. Department of Energy. The government reserves certain rights with respect to this invention.

[0003] The present invention relates to the formation of a cell having an electrolyte that has been found to function together with a negative electrode incorporating a high-capacity silicon dioxide active material, while achieving good cycling ability. [Background technology]

[0004] Lithium batteries are widely used in consumer electronics due to their relatively high energy density. For some currently available batteries, the negative electrode material may be graphite, while the positive electrode material may include lithium cobalt oxide (LiCoO2), lithium manganese oxide (LiMn2O4), lithium iron phosphate (LiFePO4), lithium nickel oxide (LiNiO2), lithium nickel cobalt oxide (LiNiCoO2), lithium nickel cobalt manganese oxide (LiNiMnCoO2), lithium nickel cobalt aluminum oxide (LiNiCoAlO2), and others. Regarding the negative electrode, lithium titanate is a graphite alternative with good cycling properties but a lower energy density. Other graphite alternatives such as tin oxide and silicon may offer increased energy density. However, some high-capacity negative electrode materials, particularly silicon, have proven commercially unsuitable due to high irreversible capacity loss associated with structural changes and very large volume expansion related to lithium intercalation / alloying, as well as insufficient discharge and charge cycles. Structural changes and large volume changes may impair the structural integrity of the electrodes, potentially leading to a decrease in cycling efficiency. [Overview of the project] [Means for solving the problem]

[0005] In the first embodiment, the present invention is A negative electrode comprising approximately 75% to 92% by weight of an active material, approximately 1% to 7% by weight of nanoscale conductive carbon, and approximately 6% to 20% by weight of a polymer binder, wherein the active material comprises approximately 35% to 95% by weight of a silicon dioxide-based material and approximately 5% to 65% by weight of graphite; Formula LiNi x Mn y Co zA positive electrode comprising lithium nickel cobalt manganese oxide, conductive carbon, and a polymer binder, which is roughly represented by O2 (wherein x+y+z≈1, 0.3≦x, 0.025≦y≦0.35, and 0.025≦z≦0.35); A separator between the negative and positive electrodes; An electrolyte comprising approximately 1 M to approximately 2 M lithium salt and a non-aqueous solvent, wherein the non-aqueous solvent comprises at least approximately 5 volume percent fluoroethylene carbonate and at least approximately 25 volume percent total amounts of dimethyl carbonate, methyl ethyl carbonate, and diethyl carbonate; A container that surrounds other cell components and Regarding lithium-ion cells, including those mentioned.

[0006] In a further embodiment, the present invention is A negative electrode comprising approximately 75% to 92% by weight of an active material, approximately 1% to 7% by weight of nanoscale conductive carbon, and approximately 6% to 20% by weight of a polymer binder, wherein the active material comprises approximately 40% to 95% by weight of a silicon dioxide-based material and approximately 5% to 60% by weight of graphite; Formula LiNi x M y Co z A positive electrode comprising nickel-rich lithium nickel-cobalt metal, conductive carbon, and a polymer binder, generally represented by O2 (wherein x+y+z≈1, 0.3≦x, 0.025≦y≦0.35, 0.025≦z≦0.35, and M is Mn, Al, Mg, Sr, Ba, Cd, Zn, Ga, B, Zr, Ti, Ca, Ce, Y, Nb, Cr, Fe, V, or a combination thereof); A separator between the negative and positive electrodes; An electrolyte comprising approximately 1 M to approximately 2 M lithium salt and a non-aqueous solvent, wherein the non-aqueous solvent comprises at least approximately 5 volume percent fluoroethylene carbonate and at least approximately 25 volume percent total amounts of dimethyl carbonate, methyl ethyl carbonate, and diethyl carbonate; A container that surrounds other cell components and Regarding lithium-ion cells, including those mentioned.

[0007] In some embodiments, a lithium-ion cell can be cycled at a charge rate of 1C and a discharge rate of 1C for at least about 700 cycles without a capacity degradation of more than 20% relative to the third cycle capacity. [Brief explanation of the drawing]

[0008] [Figure 1] This is a magnified view of a pouch battery with a battery core separated from two parts of the pouch case. [Figure 2] Figure 1 is a perspective view of the assembled pouch battery. [Figure 3] Figure 2 is a bottom view of the pouch battery. [Figure 4] An embodiment of a battery core including an electrode stack is shown. [Figure 5] This is a combination of plots of specific discharge capacity as a function of cycle count for three coin cell formats, each with a negative electrode made of a silicon oxide / carbon composite particle and graphite blend and a positive electrode made of LiNi0.6Mn0.2Co0.2O2 (NMC622) or LiNi0.8Mn0.1Co0.1O2 (NMC811), cycled over the voltage ranges of (NMC622) 4.35V~2.5V or 4.30V~2.5V or (NMC811) 4.20V~2.5V, where the initial discharge capacity is obtained in the order listed from highest to lowest. [Figure 6] Figure 5 shows a combination of plots of normalized relative discharge capacity as a function of cycle number for the three coin cells used to produce the results plotted. [Figure 7] This is a plot of normalized capacity as a function of cycle number for coin cells cycled at a charge / discharge rate of 1C, using NMC622 cathode active material and SiO composite / graphite mixed anode active material, formed with six different electrolytes, two of which contain ethylene carbonate and four of which do not. [Figure 8] This is a plot of normalized capacity as a function of cycle count for five coin cells that are identical to those used in Figure 7, except that they were cycled at a 2C charge / discharge rate. [Figure 9] This is a plot of normalized capacity as a function of cycle number for coin cells cycled at a charge / discharge rate of 1C, with the cell formed as shown in Figure 7, except that one of the six electrolytes has varying amounts of fluoroethylene carbonate as shown in Table 3. [Figure 10] This is a plot of unnormalized specific volume, referenced in comparison to the corresponding cathode active material weight in Figure 9. [Figure 11] This is a plot of normalized capacity as a function of cycles for coin cells cycled at a charge / discharge rate of 1C, with the cell being formed as shown in Figure 7, except that one of the six electrolytes has various amounts of dimethyl carbonate, ethyl methyl carbonate, and diethyl carbonate as shown in Table 3. [Figure 12] This is a plot of normalized capacity as a function of the number of cycles for coin cells that are equal to those used in Figure 11, except that the cells were cycled at a charge / discharge rate of 2C. [Figure 13] This is a plot of normalized capacity as a function of cycle number for coin cells cycled at a charge / discharge rate of 1C, with the cell formed as shown in Figure 7, except that one of the three electrolytes is used with an optional additive. [Figure 14] This is a plot of unnormalized specific volume, referenced in comparison to the corresponding cathode active material weight in Figure 13. [Figure 15] This is a plot of normalized capacity as a function of cycle number, performed at a charge / discharge rate of 1C, for a coin cell formed with the same NMC811 cathode active material and a negative electrode as used in the cell in Figure 7, and with electrolyte Electrolyte 2 from Table 3. [Figure 16]This is a plot of normalized capacity as a function of the number of cycles for a coin cell that is equal to the one used in Figure 15, except that the cycles were performed at a 2C charge / discharge rate. [Figure 17] This is a front view of a pouch cell designed for operation at approximately 11 Ah. [Figure 18] Figure 17 is a side view of the pouch cell. [Figure 19] This is a plot of discharge capacity as a function of cycle count for two pouch cells using graphite and NMC622-based cathodes and blended silicon dioxide / carbon, cycled over a voltage range of 4.3V to 2.3V. [Figure 20] This is a plot of normalized discharge capacity as a function of cycle number for the two pouch cells used to produce the results in Figure 19. [Figure 21] This is a plot of capacity as a function of cycles for cells using a cathode with NMC811 active material and an improved silicon dioxide-based anode as described herein. [Figure 22] This is a plot of normalized capacity as a function of cycles with respect to the cells used to create the plot in Figure 21. [Figure 23] This is a plot of normalized capacity as a function of cycles with a charge / discharge rate of 1C for a pouch cell formed by an NMC622 cathode active material, a SiOx composite graphite mixture anode active material, and one of three electrolyte formulations from Table 3. [Figure 24] This is a plot of discharge capacity as a function of cycle number for the pouch cell used to create Figure 23. [Figure 25] This is a plot of normalized discharge capacity as a function of cycles for coin cells formed by a positive electrode having nickel-rich NCM and a blend of lithium and manganese-rich NCM, and the negative electrode used in the examples, and the plot is shown for five different electrolytes. [Figure 26]This is a plot of unnormalized discharge capacity as a function of cycles for the cells used to create Figure 25. [Modes for carrying out the invention]

[0009] A novel electrolyte composition has been discovered that provides unprecedented cycling performance for batteries containing a negative electrode with a substantial amount of silicon-based active material to achieve high specific capacity. This achievement builds upon previous research that provides substantial improvements to negative electrode design, resulting in a significant leap in cycling performance. The novel electrolyte formulation uses a substantial amount of fluoroethylene carbonate solvent, excludes other unstable components, and appropriately selects other solvent components to provide stability. In the negative electrode, the active material is a blend with silicon-based active materials such as silicon oxide, but can be designed to include a blend with a substantial amount of graphite. Furthermore, binder characteristics have been found to contribute significantly to cycling stability. In previous studies, more than 600 cycles of cycling were achieved before reaching 80% of the initial capacity, with respect to a reasonable discharge rate and high specific capacity. Further improved studies described herein have achieved more than 800 cycles of cycling before reaching 80% of the initial capacity, with respect to a reasonable discharge rate and high specific capacity. The improved cycling performance is a significant achievement for the use of batteries in electric vehicle applications.

[0010] Lithium is used in both primary and secondary batteries. Attractive features of lithium for cell or battery applications include its light weight and the fact that it is the most electronegative metal, aspects of which can be advantageous in lithium-based batteries. Certain forms of metals, metal oxides, and carbon materials are known to incorporate lithium ions from the electrolyte into their structure by intercalation, alloying, or similar mechanisms. The positive electrode of a lithium-based battery generally contains an active material that reversibly intercalates / alloys with lithium. A lithium-ion cell generally refers to a cell in which the negative electrode active material is also a lithium intercalating / alloying material. Where used herein and for convenience, the terms cell and battery and their variations are used interchangeably unless otherwise explicitly distinguished.

[0011] The batteries described herein are lithium-ion batteries that use a non-aqueous electrolyte solution containing lithium cations and appropriate anions. In a secondary lithium-ion battery during charging, oxidation occurs at the cathode (positive electrode), where lithium ions are extracted and electrons are released. During discharge, reduction occurs at the cathode, where lithium ions are inserted and electrons are consumed. Similarly, during charging, reduction occurs at the anode (negative electrode), where lithium ions are taken in and electrons are consumed. Also, during discharge, oxidation occurs at the anode, releasing lithium ions and electrons. Unless otherwise specified, the performance values ​​described herein are at room temperature, i.e., approximately 23±2°C.

[0012] The term "element" in this specification means that when an element is present in a composition, it is shown to be in an appropriate oxidation state and in an elemental form M 0 It is used in the traditional sense to mean a member of the periodic table. Therefore, metallic elements generally exist only in the metallic state of their elemental form or in appropriate alloys of the elemental forms of metals. That is, metal oxides or other metallic compositions other than metallic alloys are generally not metals.

[0013] When using lithium-ion batteries, the uptake and release of lithium from the positive and negative electrodes induces changes in the structure of the electroactive material. As long as these changes are inherently reversible, the capacity of the material does not change with each cycle. However, to varying degrees, a decrease in the capacity of the active material with each cycle has been observed. Therefore, after a number of cycles, the cell performance falls below acceptable limits, and the cell is replaced. Furthermore, in the first cycle of a cell, an irreversible capacity loss generally occurs that is significantly larger than the capacity loss per cycle in subsequent cycles. Irreversible capacity loss (IRCL) is the difference between the charge capacity of a new cell and its first discharge capacity. A lithium metal oxide-based positive electrode may exhibit some IRCL, resulting in some replenishment of lithium to the negative electrode in terms of lithium available for the cycle. Irreversible capacity loss can lead to a corresponding decrease in the cell's capacity, energy, and power due to changes in the cell material between initial cycles.

[0014] Elemental silicon and other silicon-based active materials are attracting considerable attention as candidates for anode materials due to silicon's extremely high specific capacity for lithium uptake and release. Elemental silicon forms alloys with lithium, and theoretically, it is possible to have a lithium content corresponding to 5 or more lithium atoms per silicon atom (e.g., Li 4.4Si). Accordingly, the theoretical specific capacity of silicon is on the order of 4000 to 4400 mAh / g, which is significantly greater than the theoretical capacity of about 370 mAh / g for graphite. Graphite is believed to intercalate lithium to a level of about 1 lithium atom for 6 carbon atoms (LiC₆). In addition, elemental silicon, silicon alloys, silicon composites and the like may have a low potential relative to lithium metal similar to graphite. However, silicon undergoes a very large volume change due to alloying with lithium. A large volume expansion of about 2 to 3 times or more of the initial volume is observed, and the large volume change is associated with a significant decrease in the cycling stability of batteries having silicon-based negative electrodes. Silicon suboxide, that is, SiO where x < 2 x has also been found to be a desirable active material for lithium-based batteries. In some embodiments, this can have a high specific capacity for lithium alloying. By reference to silicon suboxide, silicon dioxide can be recognized as the fully oxidized form of silicon. For convenience, silicon suboxide may generally be referred to as silicon oxide, which is not limited to silicon monoxide (SiO) unless specifically indicated otherwise.

[0015] In particularly interesting embodiments, silicon-based active materials may include elemental silicon and / or silicon dioxide as the primary active material. Silicon dioxide has been shown to be particularly effective in achieving long-term cycling stability. Carbon can be incorporated into the composite active material to stabilize the silicon-based active material and to increase its electrical conductivity. With respect to carbon composites using nanoscale elemental silicon and / or silicon dioxide, long-term cycling stability remains challenging, but the applicant has achieved adequate cycling stability for consumer electronics applications. Herein, long-term cycling stability is described based on a mixture of electroactive graphite and silicon-based composites, in addition to other electrode design improvements. As will be described in detail below, stabilized silicon-based electrodes may further include additional conductive sources such as nanoscale carbon and improved binder blends that also significantly contribute to cycling stability.

[0016] While improved electrode design significantly enhances cycling performance, it has been found that further cycling stability can be achieved through improved electrolyte formulations. The improved electrolyte is based on a solvent containing at least 5 volume percent of fluoroethylene carbonate and at least 25 volume percent of dimethyl carbonate, ethyl methyl carbonate, diethyl carbonate, or a mixture thereof. In addition, in some embodiments, the electrolyte should essentially be free of ethylene carbonate. The electrolyte further contains about 1 M to about 2 M of electrolyte salt.

[0017] Fluorinated solvents have been found to be particularly useful for silicon-based active materials. Previous results were obtained with commercially available electrolytes containing a proprietary fluorinated solvent described in the concurrently pending U.S. Patent Application Publication 15 / 948,160 to Venkatachalam et al., currently published as U.S. Patent Application Publication 2019 / 0207209A1, entitled “Electrodes with Silicon Oxide Active materials for Lithium Ion Cells Achieving High Capacity, High Energy Density and Long Cycle Life Performance,” which is incorporated herein by reference. The use of fluoroethylene carbonate as a suitable solvent for low-temperature cell performance is recognized in U.S. Patent Application Publication 2013 / 0157147 to Li et al. (hereinafter referred to as the '147 application), entitled “Low Temperature Electrolyte for High Capacity Lithium Based Batteries,” which is incorporated herein by reference.

[0018] The use of fluoroethylene carbonate for the formation of solid electrolyte interphase layers is described by reference herein by Markevich et al., “Fluoroethylene Carbonate as an Important Component for the Formation of an Effective Solid Electrolyte Interphase on Anodes and Cathodes for Advanced Li-Ion Batteries,” ACS Energy Letters 2017, 2, 1137-1345. Markevich’s article suggests utility for silicon nanowire-based anodes. The focus of Markevich’s article is its use in high-voltage cathodes compared to ethylene carbonate-based electrolytes. This study extends previous research in '147 application, which combined superior electrode formation to achieve unprecedented silicon-based cell performance. In particular, this study demonstrates the effective use of FEC-based electrolytes for silicon oxide / graphite blend anodes in high-load and commercially viable electrode designs.

[0019] In this specification, active materials for lithium-ion secondary cells generally include, for example, cathode active materials having a moderately high average voltage relative to lithium, and silicon-based active materials for the anode. Generally, a variety of cathode materials can be used. For example, commercially available cathode active materials can be used together with existing commercially available products. Such cathode active materials include, for example, lithium cobalt oxide (LiCoO2), LiNi 1 / 3 Mn 1 / 3 Co 1 / 3 Examples include O2 (L333 or NMC111), LiNiCoAlO2 (NCA), other lithium nickel manganese cobalt oxides (NMC), LiMn2O4 (lithium manganese spinel oxide), modified forms thereof, or mixtures thereof.

[0020] Nickel-rich lithium nickel-cobalt manganese oxide (LiNi x Mn y Co z O2 (0.45 ≤ x, 0.05 ≤ y, z ≤ 0.35) may be of interest to lithium cobalt oxide due to its lower cost, lower flammability risk, and higher voltage cycling capability. As a result, nickel-rich lithium nickel manganese cobalt oxide active materials combined with an improved silicon-based anode form cells with superior cycling stability. Furthermore, lithium oxide metal materials having a layered crystalline structure and being lithium-rich relative to a LiMO2 (M = non-lithium metal) reference composition, and possessing high specific capacity, are described, for example, in U.S. Patent No. 8,389,160 to Venkatachalam et al., titled "Positive Electrode Materials For Lithium Ion Batteries Having a High Specific Discharge Capacity And Processes for the Synthesis of These Materials" (hereinafter, the '160 patent), and in U.S. Patent No. 8,465,873 to Lopez et al., titled "Positive Electrode Materials for High Discharge Capacity Lithium Ion Batteries" (hereinafter, the '873 patent), both of which are incorporated herein by reference. These materials may be described as high-capacity manganese-rich compositions (HCMR™). Blends of lithium-rich + manganese-rich NMC and nickel-rich NMC cathode active material compositions may also be used.

[0021] In particular, formula LiLe x Mn y Co zDesired cycling results can be obtained from nickel-rich lithium nickel manganese cobalt oxide (N-NMC), which can be represented by O2 (where x≧0.3 and x+y+z≈1). Commercially available formulations of these compounds include, for example, LiNi 0.33 Mn 0.33 Co 0.33 O2 (BASF and Targray (Canada)), LiNi 0.5 Mn 0.3 Co 0.2 O2 (BASF), LiNi 0.6 Mn 0.2 Co 0.2 O2 (Targray (Canada), Umicore (Belgium) and L&F Company (Korea)), LiNi 0.8 Mn 0.1 Co 0.1 This includes O2 (Targray, Canada, LG Chemical, Umicore (Belgium), and L&F Company (Korea)). Industrially, NCM and NMC are listed with cobalt and manganese in the corresponding order, both of which are used interchangeably here, and the presentation is equal, based solely on personal preference.

[0022] As described above, silicon-based electrodes present challenges in achieving adequate cycling for commercial applications. For consumer electronics applications, an adequate cycling target may be around 250–450 cycles without unacceptable performance loss, but higher cycling stability is desirable for automotive and similar higher-capacity applications. The applicant has achieved an appropriate cell design for consumer electronics applications that can achieve adequate performance using a silicon-based anode. These batteries are described in U.S. Patent Application Publication 2015 / 0050535 (hereinafter, '535 application) by Amiruddin et al., entitled “Lithium Ion Batteries With High Capacity Anode Material and Good Cycling for Consumer Electronics,” which is incorporated herein by reference. The novel electrode design herein provides cycling beyond the target cycling stability for consumer electronics and achieves adequate performance for automotive and other high-capacity applications.

[0023] Similar to silicon, oxygen-deficient silicon oxide, such as silicon dioxide (SiO₂), is also available. x(0.1 ≤ x ≤ 1.9) allows oxygen-deficient silicon oxide to be intercalated / alloyed with lithium so that it can function as an active material in lithium-based cells. Silicon oxide can incorporate relatively large amounts of lithium so that the material can exhibit a large specific capacity. However, it has also been observed that silicon oxide generally has a capacity that decreases relatively rapidly with cell cycling. Commercial silicon-based materials containing SiO, which may be present in composites with carbon and silicon nanocrystals from several suppliers, are available from Alfa Aesar (USA), Sigma-Aldrich (USA), Shin-Etsu (Japan), Osaka Titanium Corporation (Japan), and Nanostructured and Amorphous Materials Corp. (USA). Additional particularly suitable formulations of silicon-based compositions are described below. The applicant has achieved cycling stabilization of silicon oxide-based active materials using the electrode formulations described herein. In some embodiments, it may be desirable to extend the cycling life of the anode, including a combination of graphite-like carbon active material and silicon-based active material, with an acceptable reduction in specific capacity. The superior cycling performance described herein is achieved by using such active material blends.

[0024] To obtain the results described herein, the anode may include several design improvements that can be considered individually or in combination to provide improved cycling performance, and in at least some embodiments, a combination of specific electrode features may result in a remarkable synergistic performance improvement with respect to longer cycling stability. The electrolytes described herein further utilize these electrode improvements. In particular, the anode may be designed with a composite binder having high tensile strength while introducing some elongation capability. Nanoscale conductive carbon, such as carbon nanotubes, carbon black, carbon nanofibers, or combinations thereof, as conductive electrode additives has been found to improve the cycling of anodes using silicon-based active materials. These features can be combined with electrode loading and density design that provides good energy density-based performance with respect to the resulting consumer electronics cell designs. Cycling can be further improved by adding complementary lithium to the cell and / or balancing the active materials in each electrode.

[0025] The graphite component of the active material blend in the anode can provide conductivity. However, with respect to cycling, it has been found that an appropriate amount of nanoscale carbon can further stabilize the anode. Nanoscale carbon can take the form of carbon nanotubes, carbon nanofibers, or carbon nanoparticles, such as carbon black. The usefulness of nanoscale conductive carbon for the cycling stability of silicon-based anodes has been previously discovered as described in U.S. Patent No. 9,190,694B2 to Lopez et al., entitled "High Capacity Anode Materials for Lithium Ion Batteries," and U.S. Patent No. 9,780,358B2 to Masarapu et al., entitled "Battery Designs With High Capacity Anode Materials and Cathode Materials," both of which are incorporated herein by reference. Generally, electrodes contain at least about 1 wt% nanoscale conductive carbon to achieve stable cycling.

[0026] In lithium-ion cells, lithium reactive with respect to cycling is generally provided in the positive electrode active material, which migrates to the negative electrode during the initial charge of the cell, where it becomes available for discharge. Silicon-based negative electrodes can generally exhibit large irreversible capacity losses during the first charge of the cell. The capacity loss can generally be related to the corresponding irreversible changes to the material during the initial charge of the cell. For example, a solid electrolyte intermediate phase (SEI) layer forms in association with the negative electrode active material as a result of a reaction with the typical electrolyte used in the cell. It will be doneIf a stable SEI layer is formed, the SEI layer can stabilize the cell between cycling cycles. It is also likely that other irreversible changes occur with respect to the silicon-based active composition. The irreversible capacity loss in the first cycle is generally significantly greater than any per-cycle capacity loss associated with subsequent cycling of the cell, although in the second, third, and some additional cycles, the per-cycle capacity loss may still be large due to the carryover of initial changes to the first few cycles rather than being fully reached in the first cycle. Relatively large irreversible capacity loss (IRCL) can also reduce cycling capacity, as well as the energy and power output of the cell between cycling cycles. In larger format cells, capacity may increase with fewer cycles due to practical effects, such as improved electrolyte penetration through the electrode stack.

[0027] To reduce the loss of energy and power output of the cell as a result of irreversible capacity loss, complementary lithium can be introduced to provide additional lithium to the cell. The introduction of complementary lithium makes it possible to reduce the introduction of cathode active material that does not cycle due to the loss of active lithium capacity associated with IRCL. Complementary lithium means active lithium introduced directly or indirectly into the cell, which is separate from the cathode active material and replaces the lost lithium in an irreversible process and provides other beneficial effects. The applicant has found that cycling can be further stabilized by providing complementary lithium in an amount greater than that corresponding to the replenishment of irreversible capacity loss. With respect to lithium-rich + manganese-rich nickel-manganese-cobalt oxide cathode active material, this cycling stabilization is described in U.S. Patent No. 9,166,222 to Amiruddin et al. (hereinafter, the '222 patent), which is incorporated herein by reference, entitled “Lithium Ion Batteries With Supplemental Lithium”.

[0028] For example, various approaches can be used to introduce complementary lithium, including the addition of lithium-active materials (e.g., lithium metal powder or foil) to the negative electrode, the addition of a sacrificial lithium source to the positive electrode, the incorporation of a sacrificial lithium electrode into the cell structure, and electrochemical pre-lithification of the negative electrode. These approaches are described in more detail in the '222 patent and U.S. Patent No. 9,190,694 to Lopez et al., entitled "High Capacity Anode Materials for Lithium Ion Batteries" (hereinafter, the '694 patent), both of which are incorporated herein by reference. In some embodiments, it has also been found that electrochemical approaches, such as the approach described in Grant et al.'s PCT application International Publication No. 2013 / 082330, entitled "Method for Alkylating Anodes," which are incorporated herein by reference, may be advantageous. Generally, complementary lithium can be introduced in an amount that compensates for a portion of the irreversible capacity loss, almost all of the irreversible capacity loss, or more than the irreversible capacity loss, but generally, it is less than 30% of the capacity of the negative electrode active material compared to the irreversible capacity loss. In some embodiments, complementary lithium can compensate for about 90% to about 200% of the irreversible capacity loss of the anode in the first cycle.

[0029] Previous research by the applicant has shown that the use of a high-tensile-strength polymer binder, which can be filled with a suitable polyimide, significantly accelerates the cycling of silicon-based anodes. In particular, the tensile strength of the polymer binder can be at least about 60 MPa. To further extend cycling stability, it has been found that polymer binder blends can provide even more improved cycling performance. One component of the polymer binder blend may be a high-tensile-strength polymer such as polyimide, and a second polymer may have a lower Young's modulus (elastic modulus) to provide a more elastic polymer such as polyvinylidene fluoride, carboxymethylcellulose, styrene-butadiene rubber, lithified polyacrylic acid, or a mixture thereof. The polymer binder also provides good adhesion so that the electrodes remain laminated to the current collector while providing tensile strength. vinegar The desired blend may comprise at least about 50% by weight of a high-tensile-strength polymer and at least about 5% by weight of a polymer binder having a Young's modulus of about 2.4 GPa or less and, in some embodiments, an elongation of at least about 35%.

[0030] Anode design generally involves balancing coefficients to achieve target capacity while providing reasonable cycling. The incorporation of the desired electrolyte in this specification significantly further extended cycling stability. As seen in the results of the following examples, batteries using silicon-based anode active materials enabled more than 750 cycles while maintaining more than 80% of the cell capacity. At the same time, a practical negative electrode design, when combined with a suitable positive electrode design, can achieve good cycling and high energy density. Electrode designs are described in detail below, as well as the balance of design features required to achieve these results.

[0031] Generally, the electrode designs described herein are adaptable to cylindrical cells or more rectangular or prismatic batteries. Cylindrical batteries generally have a wound electrode structure, while prismatic batteries may have wound or stacked electrodes. Generally, to achieve the desired performance capacity with an appropriate electrode design in terms of electrode loading and density, a cell may include multiple electrodes of each polarity that can be stacked together with separator material between the electrodes of the cell. By winding the electrodes, a similar effect can be achieved with appropriate internal resistance for good electron conductivity and ion mobility, as well as good packing of the electrodes in a suitable container. The size of the battery generally affects the total capacity and energy output of the cell. The designs described herein are based on obtaining a desired high energy density while providing the desired cycling of the cell based on a silicon-based active material.

[0032] The discovery of an improved electrolyte formulation resulted in a significant extension of cycling stability. In particular, cells with a significant fraction of silicon-based active material were cycled for at least 800 cycles without capacity degradation to less than 80% of the third cycle capacity at a discharge rate of C. The resulting cycling stability is suitable for use in electro-autonomous applications and similar high-capacity applications.

[0033] Typical battery characteristics The negative and positive electrode structures can be assembled into a suitable cell. As will be further explained below, the electrodes are generally formed by associating with a current collector to form the electrode structure. A separator is placed between the positive and negative electrodes to form the cell. The separator is electrically insulated while providing at least selected ionic conductivity between the two electrodes. Various materials can be used as separators. Some commercially available separator materials can be formed from polymers such as polyethylene and / or polypropylene, which are porous sheets that provide ionic conductivity. Examples of commercially available polymer separators include, for example, the Celgard® line of separator materials from Asahi Kasei (Japan). Ceramic-polymer composite materials have also been developed for separators. These ceramic composite separators can be stable even at high temperatures, and the composite materials can reduce the risk of fire. Polymer-ceramic composites for lithium-ion battery separators are marketed under the trade names Separion® by Evonik Industries, Germany and Lielsort® by Tiejin Lielsort Korea Co., Ltd. Separators can also be formed using porous polymer sheets coated with gel-forming polymers. Designs for such separators are further described in U.S. Patent No. 7,794,511B2 to Wensley et al., entitled "Battery Separator for Lithium Polymer Battery," which is incorporated herein by reference. Suitable gel-forming polymers include, for example, polyvinylidene fluoride (PVDF), polyurethane, polyethylene oxide (PEO), polypropylene oxide (PPO), polyacylonitrile, gelatin, polyacrylamide, polymethyl acrylate, polymethyl methacrylate, polyvinyl acetate, polyvinylpyrrolidone, polytetraethylene glycol diacrylate, copolymers thereof, and mixtures thereof.

[0034] The electrolyte facilitates ion transport between the anode and cathode of the battery during the charging and discharging processes. Electrolytes for lithium-ion batteries incorporate non-aqueous solvents and lithium salts. Improved electrolytes for silicon-based electrodes are described in detail below. The electrolyte is generally leached into the cell before the case is sealed.

[0035] The electrodes described herein can be assembled into a variety of commercially available cell / battery designs, such as prismatic batteries, winding cylindrical cells, coin cells, or other suitable cell / battery designs. A cell may include a single electrode pair or multiple electrode pairs assembled in parallel and / or series electrical connections. Electrode stacks may have additional electrodes such that the stack terminates with the same polarity as the other end of the stack, for convenience in placement within a container. While the electrode structures described herein can be used in batteries for primary or single-charge applications, the resulting batteries generally possess the desired cycling characteristics for secondary battery applications with multiple battery cycles.

[0036] In some embodiments, the positive and negative electrodes can be stacked with a separator between them, and the resulting stacked structure can be wound into a cylindrical or prismatic configuration to form a cell structure. Suitable conductive tabs can be welded to the current collector, and with the negative and positive electrode tabs welded to suitable external contacts, the resulting jellyroll structure can be placed in a metal canister or polymer package. The electrolyte is added to the canister, and the canister is sealed to complete the cell. Some commercially available rechargeable cells currently in use include, for example, cylindrical 18650 cells (18 mm in diameter and 65 mm in length) and 26700 cells (26 mm in diameter and 70 mm in length), but other cell / battery sizes and prismatic and foil pouch cells / batteries of selected sizes can be used.

[0037] Pouch batteries may be particularly desirable for a variety of applications, including certain vehicle applications, due to their stacking convenience and relatively low container weight. Designs of pouch batteries for vehicle batteries incorporating high-capacity cathode active materials are further described in U.S. Patent No. 8,187,752 to Buckley et al., entitled "High Energy Lithium Ion Secondary Batteries," and U.S. Patent No. 9,083,062B2 to Kumar et al., entitled "Battery Packs for Vehicles and High Capacity Pouch Secondary Batteries for Incorporation into Compact Battery Packs," both of which are incorporated herein by reference. While pouch battery designs are particularly convenient for use in certain battery pack designs, pouch batteries can be effectively used in other situations as well.

[0038] Figures 1-4 show typical embodiments of a pouch battery. In this embodiment, the pouch battery 100 includes a pouch enclosure 102, an electrode core 104, and a pouch cover 106. The electrode core is described further below. The pouch enclosure 102 includes a cavity 110 and an edge 112 surrounding the cavity. The cavity 110 has dimensions such that the electrode core 104 can be fitted inside the cavity 110. As shown in Figures 2 and 3, the pouch cover 106 is sealed around the edge 112, allowing the electrode core 104 to be sealed within the sealed battery. End tabs 114, 116 extend outward from the sealed pouch for electrical contact with the electrode core 104. Figure 3 is a schematic cross-sectional view of the battery of Figure 2 as seen along line 3-3. Many additional embodiments of the pouch battery are possible using various configurations of the edge and seal.

[0039] Figure 4 shows an embodiment of an electrode core 104 that generally includes an electrode stack. In this embodiment, the electrode stack 130 includes negative electrode structures 132, 134, 136, positive electrode structures 138, 140, and separators 150, 152, 154, 156 disposed between adjacent positive and negative electrodes. The separators can be provided as a single folded sheet in which the electrode structures are arranged within the folds of the separator. The negative electrode structures 132, 134, 136 include negative electrodes 160, 162, negative electrodes 164, 166, and negative electrodes 168, 170, respectively, disposed on either side of the current collectors 172, 174, 176. The positive electrode structures 138, 140 include positive electrodes 180, 182, positive electrodes 184, 186, respectively, disposed on the opposite side of the current collectors 188, 190. Tabs 192, 194, 196, 198, and 200 are connected to current collectors 172, 188, 174, 190, and 176, respectively, to facilitate the connection of individual electrodes in series or parallel. For vehicle applications, the tabs are generally connected in parallel, with tabs 192, 196, and 200 electrically connected to electrical contacts accessible from outside the container, and tabs 194 and 198 electrically connected to electrical contacts as opposite poles accessible from outside the container.

[0040] The electrode stack may have additional negative electrodes such that both outer electrodes adjacent to the container are negative electrodes. Generally, a battery with stacked electrodes of the dimensions described herein has 5 to 40 negative electrode elements (with current collectors coated on both sides with an active material), and in further embodiments, 7 to 35 negative electrode elements. The corresponding number of positive electrode elements is generally one less than the number of negative electrode elements. Those skilled in the art will recognize that an additional range of electrode numbers within the express range described above is conceivable and within the scope of this disclosure.

[0041] As described above, wound electrodes can be used in conjunction with either cylindrical or substantially prismatic batteries. A wound cell for cylindrical lithium-ion batteries is further described in U.S. Patent No. 8,277,969 to Kobayashi et al., titled “Lithium Ion Secondary Battery,” which is incorporated herein by reference. A prismatic battery with wound electrodes is described in U.S. Patent No. 7,700,221 to Yeo ('221 patent), titled “Electrode Assembly and Lithium Ion Secondary Battery Using the Same,” which is incorporated herein by reference. Neither Kobayashi's '969 patent nor Yeo's '221 patent describes a method for achieving suitable cycling or high energy density using silicon-based active materials. Designs for prismatic batteries using wound electrodes are further described, for example, in the aforementioned '221 patent. Specific designs of either stacked electrode combinations or wound cells may also be influenced by the target dimensions and target capacity of the battery.

[0042] The improved negative electrode can be used for a variety of applications and cell / battery designs. Regarding the electrode stack, the electrode area can be appropriately selected based on volume and design constraints for a particular application. The following discussion focuses on large cells generally designed for vehicle applications such as drones, automobiles, trucks, or other vehicles. However, the improved negative electrodes described herein can be effectively used for consumer electronics applications, which can be based on smaller cell configurations. It should also be noted that automobiles can use smaller consumer electronics cells, and Tesla vehicles are currently known to use thousands of these small consumer electronics cells in their battery packs. Generally, within a certain range, larger cells / batteries can achieve higher energy densities. It may be desirable to select the positive electrode active material based on the specific application to balance various considerations, such as energy density.

[0043] By selecting electrode parameters, the design of a high-gravimetric energy density cell can incorporate a balance of elements such as electrode area, number of electrode structures, and battery capacity. Electrode area refers to the spatial extent of a single electrode along one side of the current collector. Figure 1 shows the length "L," and Figure 3 shows the width "W" of the electrode. As shown in the figures, the electrode area can be defined as L × W. In some embodiments, the area of ​​each electrode can be similar so that the dimensions of the battery, including the electrode stack, can have lengths and widths similar to those of each electrode in the stack. In some embodiments, the separator may be sheet-like with an area slightly larger than the area of ​​the electrodes, and in some embodiments, the separator may be formed to be folded, pleated, or have pockets, with the electrodes positioned in the pleats or pockets of the separator.

[0044] electrolyte The inventors refer to a solution containing solvated ions as an electrolyte, and an ionic composition that dissolves in a suitable liquid to form solvated ions as an electrolyte salt. Electrolytes for lithium-ion batteries may include one or more selected lithium salts, a non-aqueous solvent, and optional additives. Desired electrolytes for achieving unprecedented cycling described herein have a well-selected solvent and, in particular, avoid components that have been found to degrade cycling performance.

[0045] Suitable lithium salts generally have an inert anion. Suitable lithium salts include, for example, lithium hexafluorophosphate, lithium hexafluoroarsenate, lithium bis(trifluoromethylsulfonylimide), lithium trifluoromethanesulfonate, lithium tris(trifluoromethylsulfonyl)methide, lithium tetrafluoroborate, lithium perchlorate, lithium tetrachloroaluminate, lithium chloride, lithium difluorooxalatoborate, and combinations thereof. Lithium hexafluorophosphate and lithium tetrafluoroborate are of particular interest. In some embodiments, the electrolyte includes a lithium salt at a concentration of 1 M to 2 M, in further embodiments about 1.1 M to about 1.9 M, and in other embodiments about 1.25 M to about 1.8 M. Those skilled in the art will recognize that additional ranges of electrolyte salt concentrations within the above express ranges are considered and within the scope of this disclosure.

[0046] Regarding interesting lithium-ion batteries, non-aqueous liquids are generally used to dissolve lithium salts in non-aqueous solvents. Solvents generally do not dissolve electrically active materials. The choice of solvent is important with respect to the electrolytes described herein, which provide remarkably improved cycling performance. Generally, the solvents contain about 5% to about 30% by weight of fluoroethylene carbonate (FEC), about 7% to about 27% by weight in further embodiments, and about 8% to about 25% by weight in additional embodiments. Correspondingly, solvents generally contain substantially no ethylene carbonate, as ethylene carbonate has been found to be detrimental with respect to cycling. Ethylene carbonate has a melting point of about 35°C and is solid at room temperature. Fluoroethylene carbonate melts at approximately room temperature, 18–23°C. Electrolytes with fluoroethylene carbonate have also been found to have excellent low-temperature performance, as described in the above-mentioned '147 application'.

[0047] The electrolyte solvent generally includes a liquid component at room temperature, and solvents of particular interest further include linear carbonate esters and optional additives. Desired linear carbonate esters include, for example, dimethyl carbonate, ethyl methyl carbonate, and diethyl carbonate. In some embodiments, the total volume to which dimethyl carbonate, ethyl methyl carbonate, and diethyl carbonate are added to the solvent is about 50% to about 95% by volume, in further embodiments about 55% to about 92.5% by volume, and in additional embodiments about 60% to about 91% by volume. In some embodiments, the solvent essentially consists of fluoroethylene carbonate and one or more dimethyl carbonate, ethyl methyl carbonate, and diethyl carbonate. Those skilled in the art will recognize that an additional range of solvent components within the express range described above is considered and within the scope of this disclosure.

[0048] In some embodiments, the solvent may further comprise propylene carbonate and / or fluorobenzene. If one or both of these optional solvent components are present, the solvent may generally contain one or both of these solvent components in amounts of about 0.5% to about 12% by volume, about 0.75% to about 10% by volume in further embodiments, and about 1% to about 8% by volume in other embodiments. While the PC or FB solvent components do not significantly alter the cycling performance, these solvent components may be desirable due to processing advantages such as reduced gas formation. Those skilled in the art will recognize that additional ranges of PC and / or FB solvent concentrations within the express range described above are considered and within the scope of this disclosure.

[0049] Generally, the solvent may contain other trace components in amounts of about 20% by volume or less of the total amount of these other solvent components, about 10% by volume or less in some embodiments, about 0.01% to about 5% by volume in other embodiments, and about 0.1% to about 1% by volume in further embodiments. Those skilled in the art will recognize that an additional range of solvent components within the express range described above is considered and within the scope of this disclosure. Other suitable solvent components that may be present in trace amounts and optionally in some embodiments include, for example, 2-methyltetrahydrofuran, dioxolane, tetrahydrofuran, γ-butyrolactone, dimethyl sulfoxide, acetonitrile, formamide, dimethylformamide, triglyceride (tri(ethylene glycol)dimethyl ether), diglyceride (diethylene glycol dimethyl ether), DME (glyceride or 1,2-dimethyloxyethane or ethylene glycol dimethyl ether), nitromethane, and mixtures thereof. Other trace fluorinated solvent components may include, for example, fluorinated vinyl carbonate, monochloroethylene carbonate, monobromoethylene carbonate, 4-(2,2,3,3-tetrafluoropropoxymethyl)-[1,3]dioxolan-2-one, 4-(2,3,3,3-tetrafluoro-2-trifluoromethylpropyl)-[1,3]dioxolan-2-one, 4-trifluoromethyl-1,3-dioxolan-2-one, bis(2,2,3,3-tetrafluoropropyl) carbonate, bis(2,2,3,3,3-pentafluoropropyl) carbonate, or mixtures thereof. Additional fluorinated trace solvent components include, for example, the fluorinated ether described in U.S. Patent Application Publication No. 2018 / 0062206 to Li et al., entitled “Fluorinated Ether as Electrolyte Co-Solvent for Lithium Metal Based Anode,” and the fluorinated ether described in International Publication No. 2018 / 051675 to Takuya et al., entitled “Lithium Secondary Battery.”

[0050] Common solvent compounds generally considered desirable solvent components for lithium-ion cells have been found to be detrimental to the cycling of the improved electrodes described herein. In particular, ethylene carbonate is generally excluded from the electrolytes described herein. Therefore, the electrolytes generally contain 0.1% by volume or less of ethylene carbonate.

[0051] Electrode structure The electrodes of a cell contain an active material along with a binder and conductive additives. The electrodes are formed into sheets, dried, and pressed to achieve the desired density and porosity. Generally, electrode sheets are formed directly on a metal current collector, such as a metal foil or a thin metal grid. In many cell structures, electrode layers are formed on both sides of the current collector to provide the desired performance in the assembled cell or battery. The electrode layers on both sides of the current collector are at the same potential within the cell and can therefore be considered elements of the same electrode structure; however, the current collector itself, although part of the electrode structure, is electrochemically inert and is therefore generally not considered part of the electrode. Thus, a reference to the physical aspect of an electrode generally refers to a single electrode composition within an electrode structure. Conductive current collectors can facilitate the flow of electrons between the electrode and the external circuit.

[0052] In some embodiments, when a high loading level is used for the positive or negative electrode, the electrode density can decrease, providing good cycling stability for the electrode. Electrode density is a function of a suitable range of press pressure. Generally, electrode density cannot be arbitrarily increased without sacrificing performance with respect to the loading level while achieving the desired cycling performance and capacity at higher discharge rates. The characteristics of specific negative and positive electrode layers are described in the following sections.

[0053] In some embodiments, the current collector can be formed from nickel, aluminum, stainless steel, copper, etc. The electrode material can be cast onto the current collector as a thin film. Next, to remove the solvent from the electrode, the electrode material can be dried together with the current collector, for example, in an oven. In some embodiments, the dried electrode material is in contact with the current collector foil or other structure at a load of about 2 to about 10 kg / cm³. 2 It is possible to subject it to a pressure of (kilograms per square centimeter). The current collector used in the positive electrode can have a thickness of about 5 to 30 microns, about 10 to 25 microns in other embodiments, and about 14 to 20 microns in further embodiments. In one embodiment, the positive electrode uses an aluminum foil current collector. The current collector used in the negative electrode can have a thickness of about 2 to 20 microns, about 4 to 14 microns in other embodiments, and about 6 to 10 microns in further embodiments. In one embodiment, the negative electrode uses copper foil as the current collector. Those skilled in the art will recognize that additional ranges of current collector thicknesses within the express ranges described above are conceivable and are within the disclosure.

[0054] negative electrode The basic electrode design comprises a blend of an active composition, a polymer binder, and a conductive diluent. As described above, in some embodiments, the improved electrode design may include a blend of polymer binder and active composition, as well as a nanoscale conductive carbon additive. In some embodiments, the active material blend may comprise a silicon-based active material, such as a silicon oxide composite, and at least 10 wt% of a separate graphite. It has also been found that stabilization of electrode cycling by the silicon-based active material can be obtained by a blend of polyimide to provide high mechanical strength, along with a more deformable polymer portion that still provides good electrode performance in a synergistic binder blend. While graphite can provide conductivity to the electrode, nevertheless, in some embodiments, the amount of a separate nanoscale conductive carbon may be significant in the ability to produce a long-cycle anode. Generally, graphite is electrochemically active, while nanoscale conductive carbon is not considered electrochemically active. These improved design embodiments are therefore incorporated into the electrode along with further previously discovered improvements to silicon-based electrodes.

[0055] There is considerable interest in high-capacity silicon-based negative electrode active materials. Silicon-based active materials have generally failed to achieve adequate cycling stability for automotive applications in batteries containing significant amounts of silicon. In application '535', successful cycling for consumer electronics applications, etc., was demonstrated with approximately 200-300 cycles at an initial capacity of at least 80%. The applicant has achieved particular success with cycling stability, primarily using silicon oxide composite-based materials. This specification provides electrodes capable of successfully cycling more than 600 cycles without reducing capacity below 80% by cycling over a wide voltage range at appropriate rates. Therefore, this study relates to extending cycling stability to a region suitable for automotive applications.

[0056] As described herein, improved cycling results can be obtained with silicon-based active materials and active compositions blended with graphite carbon. Generally, the total capacity of the negative electrode blended active material may be at least about 750 mAh / g, at a rate of C / 3, at least about 900 mAh / g in a further embodiment, at least about 1000 mAh / g in an additional embodiment, and at least about 1100 mAh / g in other embodiments when cycled against lithium metal from 5 millivolts (mV) to 1.5 V. The blended active material may contain at least about 40 wt% silicon-based active material, at least about 50 wt% silicon-based active material in a further embodiment, about 55 wt% to about 95 wt% silicon-based active material in other embodiments, and about 60 wt% to about 90 wt% silicon-based active material in an additional embodiment. Accordingly, the blended active material may include about 5% by weight to about 65% by weight of graphite, in a further embodiment about 7% by weight to about 60% by weight of graphite, in an additional embodiment about 8% by weight to about 55% by weight of graphite, and in other embodiments about 10% by weight to about 50% by weight of graphite. Those skilled in the art will recognize that additional ranges of specific discharge capacity and concentration of silicon-based active materials within the express range described above are conceivable and within the scope of this disclosure.

[0057] As described above and in detail below, suitable silicon-based active materials may include composites with carbon components. Silicon-based active materials will be described in detail in the following sections. A composite refers to a particulate material with components closely combined in a monolithic material having effective homogeneity on a suitable scale, as opposed to a blend containing a mixture held together by a polymer binder. Composite components may include, for example, silicon, oxygen, and carbon. While we do not wish to be limited by theory, generally, the carbon component of a silicon composite is not considered electrochemically active and is generally not graphite-based. However, activity is an abstract concept, as a given close combination in the composite and crystalline structure can be very complex and difficult to evaluate. In any case, it is readily understood by those skilled in the art that the carbon component of a composite is distinguishable from a separate graphite, which is not present in the composite in the active material blend. The following examples are based on commercially available composite compositions that are considered to contain mainly silicon dioxide and some amounts of elemental silicon crystals and elemental carbon in the combined composite particulate material.

[0058] Graphite is commercially available in natural and synthetic forms, and suitable graphites include natural or synthetic graphite, etc. Graphite is a crystalline form of carbon, containing covalently bonded carbon in a sheet. As used herein, graphite means graphite carbon without requiring perfect crystallinity, and some natural graphite materials may contain some crystalline impurities. However, graphite generally means a material dominated by a graphite structure as recognized in the art. Graphite is conductive along the plane of covalently bonded carbon sheets stacked in a crystal. Crystalline carbon in graphite form can intercalate lithium and is therefore an electrochemically active material established for lithium-ion batteries.

[0059] Graphite particles can have an average particle size of approximately 1 micron to approximately 30 microns, in further embodiments approximately 1.5 microns to approximately 25 microns, and in other embodiments approximately 2 microns to approximately 20 microns. Generally, to avoid an uneven electrode surface, it is considered desirable that the graphite does not contain particles larger than the electrode thickness, and graphite particles with a size significantly smaller than 1 micron may have reduced crystallinity. In some embodiments, graphite carbon can have a D50 (median mass diameter) of approximately 5 microns to approximately 50 microns, in further embodiments approximately 7 microns to approximately 45 microns, and in additional embodiments approximately 10 microns to approximately 8 microns to approximately 40 microns. Also, in some embodiments, the BET surface area of ​​the graphite carbon active material (evaluable according to ISO 4652) is approximately 1 m². 2 / g~about 100m 2 / g, in further embodiments, about 5m 2 / g~about 85m 2 / g and, in additional embodiments, approximately 7.5m 2 / g~about 60m 2 It may be / g. Those skilled in the art will recognize that an additional range of particle size and surface area of ​​graphite carbon active materials is conceivable and is within this disclosure. In contrast, conductive carbon black, etc. (called quasicrystalline), is generally about 40m 2 / g~1000m 2 It has a surface area of ​​ / g or more.

[0060] With respect to polymer binders, the applicant has obtained suitable cycling of silicon-based cells using high-tensile strength binders, such as polyimide binders. See U.S. Patent No. 9,601,228 to Deng et al. (hereinafter, the '228 patent), entitled “Silicon Oxide Based High Capacity Anode Materials for Lithium Ion Batteries,” which is incorporated herein by reference. Surprisingly, in some embodiments for obtaining longer-term cycling stability, polymer binder blends have been found to further stabilize cycling. In particular, a second polymer or combination of polymers that provides a lower modulus of elasticity (corresponding to higher elasticity) can be blended with high-tensile strength polyimide. The binder blend generally comprises at least about 50 wt% polyimide, at least about 55 wt% polyimide in further embodiments, and about 60 wt% to about 95 wt% polyimide in other embodiments. Similarly, the binder blend generally includes at least about 5 wt% of polymers having a low modulus, at least about 10 wt% in further embodiments, and in other embodiments about 12 wt% to about 40 wt% of polymers having a low modulus, as further explicitly stated below. Those skilled in the art will recognize that additional ranges of polymer amounts within the above explicitly stated ranges are conceivable and are within the disclosure. The polymers of the blend can be selected to dissolve in the same solvent.

[0061] Polyimides are polymers based on repeating units of imide monomer structures. While polyimide polymer chains can be aliphatic, for high-tensile strength applications, the polymer backbone is generally aromatic, extending along the nitrogen atoms of the polyimide structure. Regarding silicon-based anodes exhibiting significant morphological changes during cycling, thermosetting polyimide polymers have been found desirable for high-capacity anodes. This may be due to their high mechanical strength. The following table lists suppliers of high-tensile strength polyimide polymers and the names of the corresponding polyimide polymers.

[0062] JPEG0007933852000001.jpg65169

[0063] Polyimide polymers can have tensile strengths of at least about 60 MPa, at least about 100 MPa in a further embodiment, and at least about 125 MPa in other embodiments. Some commercially available polyimides with high tensile strength can also have relatively high elongation values. Elongation is the amount of stretching the polymer can withstand before it is torn. In some embodiments, polyimides can have elongation of at least about 40%, at least about 50% in a further embodiment, and at least about 55% in other embodiments. Tensile strength and elongation values ​​can be measured according to the ASTM D638-10 standard test method for tensile properties of plastics or the ASTM D882-91 standard test method for tensile properties of thin plastic sheets, both of which are incorporated herein by reference. Based on values ​​reported by commercial suppliers, the results from these different ASTM protocols appear to be similar to each other with respect to polyimides. Those skilled in the art will recognize that an additional range of polymer properties within the express range described above is conceivable and is within this disclosure.

[0064] A suitable, more flexible polymer component can be selected that is inert to the electrochemistry of the cell and compatible with processing with polyimide. In particular, suitable more flexible polymer components include, for example, polyvinylidene fluoride (PVdF), carboxymethylcellulose (CMC), styrene-butadiene rubber (SBR), lithified polyacrylic acid (LiPAA), or mixtures thereof. Regarding polymer properties, several significant properties for high-capacity anode applications are summarized in the following table.

[0065] JPEG0007933852000002.jpg66169

[0066] PVDF stands for polyvinylidene fluoride, CMC stands for sodium carboxymethylcellulose, SBR stands for styrene-butadiene rubber, and LiPAA stands for lithium polyacrylic acid. PVDF, CMC, and SBR are commercially available from many suppliers. LiPAA can be prepared from LiOH and commercially available polyacrylic acid (PAA). For example, stoichiometric amounts of LiOH can be added to a solution of PAA using 1 mole of LiOH per monomer unit of PAA. The formation and use of LiPAA are further described in Li et al., “Lithium polyacrylate as a binder for tin-cobalt-carbon negative electrodes in lithium-ion batteries”, Electrochemica Acta 55(2010)2991-2995, which is incorporated herein by reference.

[0067] Elongation refers to the elongation of the polymer before it is torn. Generally, for silicon-based materials, elongation of at least about 30%, at least about 50% in some embodiments, and at least about 70% in further embodiments is desirable. With respect to polymer binder blends, more elastic polymer binder components may be desirable to have an elastic modulus (referred to as Young's modulus or tensile modulus) of about 2.4 GPa or less, about 2.25 GPa or less in further embodiments, about 2 GPa or less in other embodiments, and about 1.8 GPa or less in additional embodiments. Those skilled in the art will recognize that an additional range of properties for more elastic polymer components within the above express ranges is conceivable and is within the scope of this disclosure.

[0068] To form electrodes, the powder can be blended with the polymer in a suitable liquid, such as a solvent for dissolving the polymer. Polyimides and PVdF can generally be processed in N-methylpyrrolidone (NMP), but other suitable organic solvents may be used. Aqueous processable polyimides are commercially available, and these are suitable for blending with a wide range of other polymers. The particulate components of the electrode, i.e., the active material and nanoscale conductive carbon, can be blended with the polymer binder blend in a solvent before forming a paste. The resulting paste can then be pressed into the electrode structure.

[0069] A large amount of active material can be loaded into the binder. In some embodiments, the anode has about 75 to about 92 wt% anode active material, in other embodiments about 77 to about 90 wt% anode active material, and in further embodiments about 78 to about 88 wt% anode active material. In some embodiments, the anode has about 6 to about 20 wt% polymer binder, in other embodiments about 7 to about 19 wt% polymer binder, and in further embodiments about 8 to 18 wt% polymer binder. Also, in some embodiments, the anode contains about 1 to about 7 wt% nanoscale conductive carbon, in further embodiments about 1.5 to about 6.5 wt%, and in additional embodiments about 2 to about 6 wt% nanoscale conductive carbon. Those skilled in the art will recognize that additional ranges of polymer loading amounts within the express range described above are conceivable and within the scope of this disclosure.

[0070] For improved cycling of the anode, nanoscale carbon additives or combinations thereof have been found to be particularly desirable. Nanoscale conductive carbon generally refers to large surface area elemental carbon particles having at least two dimensions of primary particles that are submicron. Suitable nanoscale conductive carbons include, for example, carbon black, carbon nanotubes, and carbon nanofibers. In some embodiments, the nanoscale conductive carbon additive used in the anode may include carbon nanotubes, carbon nanofibers, carbon nanoparticles (e.g., carbon black), or combinations thereof. In some embodiments, to achieve improved performance, the conductive additive may have a conductivity of at least about 40 S / cm, at least about 50 S / cm in some embodiments, and at least about 60 S / cm in further embodiments. Those skilled in the art will recognize that additional ranges of particle loading and conductivity within the express range described above are conceivable and within the scope of this disclosure.

[0071] Electrical conductivity, the reciprocal of resistance, may be reported by the supplier, and is generally measured using specific techniques developed by the supplier. For example, the electrical resistance of carbon black is measured between two copper electrodes using Super P® carbon black. See Imerys Graphite & Carbon, A Synopsis of Analytical Procedures, 2019 (http: / / www.imerys-graphite-and-carbon.com / wordpress / wp-app / uploads / 2019 / 02 / Analytical-ProceduresWeb 21Feb19.pdf). Additionally, appropriate complementary conductive additives can be added to provide longer-term cycling stability. Some suppliers also specify conductive carbon concentrations to achieve the conductive percolation threshold.

[0072] Carbon black refers to a synthetic carbon material and may also be referred to by other names such as acetylene black, furnace black, thermal black, or other names, which suggest a synthetic approach. While carbon black is generally described as amorphous carbon, at least some forms of carbon black suggest small domains ranging from short to medium in size, corresponding to the crystalline structure of graphite or diamond. However, for practical purposes, the material can be considered amorphous. According to ISO Technical Specification 80004-1 (2010), carbon black is a nanostructured material. The primary particles of carbon black can range from tens of nanometers or less, but the primary particles are generally rigidly fused into chains or other aggregates, and the smallest dispersed unit can be considered to be around 80 nm to 800 nm, still submicron in size. Carbon blacks synthesized to provide the desired level of electrical conductivity are commercially available, including Super-P® (Imerys), Ketjenblack® (Akzo Nobel), Shawinigan Black® (Chevron-Phillips), and Black Pearls 2000® (Cabot).

[0073] Carbon nanofibers are generally high-aspect-ratio fibers containing graphene layers in the form of plates, cones, or other forms, while carbon nanotubes contain graphene sheets folded within tubes. Carbon nanofibers have a diameter of 250 nm or less and are commercially available from companies such as Pyrograf® Carbon Nanofibers (Pyrograf Products, Inc.) or American Elements, Inc. Carbon nanotubes have been found to be desirable conductive additives that can improve the cycling performance of either the positive or negative electrode. Single-wall or multi-wall carbon nanotubes are also available from American Elements, Inc. (CA, USA), Canno Technologies (China), Fuji, Inc. (Japan), Alfa Aesar (MA, USA), or NanoLabs (MA, USA).

[0074] The negative electrodes used in the cells described herein can have a high active material loading level along with a sufficiently high electrode density. With respect to a particular active material loading level, density is inversely proportional to thickness; therefore, electrodes with higher density will be thinner than electrodes with lower density. The loading amount is equal to the product of density and thickness. In some embodiments, the negative electrode of the battery has at least about 1.5 mg / cm³ 2 In other embodiments, approximately 2 mg / cm³ 2 ~about 8mg / cm 2 In an additional embodiment, approximately 2.5 mg / cm³ 2 ~about 6mg / cm 2 In other embodiments, approximately 3 mg / cm³ 2 ~about 4.5mg / cm 2 The negative electrode has a negative electrode active material loading level. In some embodiments, the negative electrode of the battery is 、 Approximately 0.5 g / cc (cc = cubic centimeter (cm)) 3The active material density is approximately 2 g / cc in other embodiments, approximately 0.6 g / cc to approximately 1.5 g / cc in other embodiments, and approximately 0.7 g / cc to approximately 1.3 g / cc in additional embodiments. Similarly, the silicon dioxide-based electrode can have an average dry thickness of at least approximately 15 microns, at least approximately 20 microns in further embodiments, and approximately 25 microns to approximately 75 microns in additional embodiments. The resulting silicon dioxide-based electrode has an active material density of at least approximately 3.5 mAh / cm². 2 In a further embodiment, at least about 4.5 mAh / cm² 2 In an additional embodiment, at least about 6 mAh / cm² 2 It is possible to indicate the volume per unit area. Those skilled in the art will recognize that additional ranges of active material loading levels and electrode densities within the express range described above are conceivable and are within the scope of this disclosure.

[0075] High-capacity silicon-based anode material In general, the battery designs described herein are based on high-capacity anode active materials. Specifically, anode active materials generally have a specific capacity of at least about 800 mAh / g, at least about 900 mAh / g in a further embodiment, at least about 1000 mAh / g in an additional embodiment, at least about 1150 mAh / g in some embodiments, and at least about 1400 mAh / g in other embodiments when cycled against lithium metal at a rate of C / 10 at 0.005 V to 1.5 V. Therefore, the specific capacity of the negative electrode active material can be evaluated in cells using lithium metal counter electrodes. However, in the batteries described herein, the negative electrode can exhibit a sufficiently similar specific capacity when cycled against high-capacity lithium metal oxide positive electrode active materials. In batteries using non-lithium metal electrodes, the specific capacity of each electrode can be evaluated by dividing the battery capacity by the respective weight of the active material. As described herein, by combining silicon-based active materials and graphite-carbon active materials, good capacity can be observed and the desired cycling results can be obtained.

[0076] Elemental silicon, silicon alloys, and silicon composites can have a low potential relative to lithium metal, similar to graphite. However, elemental silicon undergoes a very large volume change upon alloying with lithium. Large volume expansions of 2 to 4 times or more of the initial volume are observed, and this large volume change is associated with a significant decrease in the cycling stability of batteries with silicon-based negative electrodes.

[0077] The cells described herein may utilize commercially available silicon dioxide, elemental silicon, and carbon composites. Other formulations of silicon-based anode active materials with high capacity and suitable cycling properties have also been developed. Several silicon-based compositions are described below that may replace commercially available SiO-based compositions and offer promising alternatives. The improved electrolyte formulations described herein have been found to be particularly effective in silicon-based anode active materials and in blends of silicon-based active materials with graphite.

[0078] Furthermore, silicon-based high-capacity materials in the negative electrode of lithium-based batteries may exhibit significant irreversible capacity loss (IRCL) in the first charge / discharge cycle of the battery in some formulations. A high IRCL in the silicon-based anode can consume a significant portion of the capacity available for the battery's energy output. Since the cathode, or positive electrode, supplies all the lithium in conventional lithium-ion batteries, a high IRCL in the anode, or negative electrode, can result in a low-energy battery. To compensate for a high anode IRCL, complementary lithium can be added directly or indirectly to the negative electrode material. The use of complementary lithium to improve the performance of silicon-based electrodes is also described in the '694' and '228' patents, both of which are incorporated herein by reference. The use of complementary lithium in improved battery designs is further described below.

[0079] The anode, or negative electrode, of the battery described herein can be made of a nanostructured active silicon-based material that better adapts to volume expansion and thus maintains mechanical electrode stability and battery cycle life. Nanostructured silicon-based negative electrode compositions are disclosed in U.S. Patent No. 9,139,441 ('441 patent) to Angucamy et al., entitled "Porous Silicon Based Anode Material Formed Using Metal Reduction," which is incorporated herein by reference. Suitable nanostructured silicon may include, for example, nanoporous silicon and nanoparticle silicon. Nanostructured silicon can also be formed into composites with carbon and / or alloys with other metallic elements. The objective of the improved silicon-based material design is to further stabilize the negative electrode material during cycling while, in some embodiments, reducing irreversible capacity loss in the first charge and discharge cycle, while maintaining high specific capacity. Let Furthermore, it has been observed that pyrolytic carbon coatings also stabilize silicon-based materials in terms of battery performance.

[0080] Desired high-capacity anode active materials may include porous silicon (pSi)-based materials and / or composites of porous silicon-based materials. Generally, pSi-based materials include highly porous crystalline silicon that can provide a high surface area and / or a high void ratio compared to bulk silicon. Nanostructured porous silicon can be formed by various approaches, such as electrochemical etching of silicon wafers, but particularly excellent battery performance was obtained from nanostructured porous silicon obtained by metal reduction of silicon oxide powder. In particular, the material has particularly excellent cycling properties while maintaining a high specific capacity. By forming composites of pSi-based materials with carbon-based materials or metals, it is possible to further mechanically stabilize the anode to improve cycling. Further descriptions of pSi-based materials from the reduction of silicon oxide can be found in the '441 patent' referenced above.

[0081] With respect to composite materials, nanostructured silicon components can be combined with, for example, carbon nanoparticles and / or carbon nanofibers within closely coupled composite materials. The components can be pulverized, for example, to form composites in which the materials closely associate. Generally, such associations are thought to have mechanical features, such as softer silicon coated on or mechanically fixed to a harder carbon material. In additional or alternative embodiments, silicon can be pulverized together with metal powder to form alloys that may have corresponding nanostructures. Carbon components can be combined with silicon-metal alloys to form multicomponent composites.

[0082] Furthermore, a carbon coating can be applied to a silicon-based material to improve its conductivity. The carbon coating also appears to stabilize the silicon-based material in terms of improved cycle life and reduced irreversible capacity loss. The desired carbon coating can be formed by thermal decomposition of an organic composition. A hard amorphous coating can be formed by thermal decomposing the organic composition at a relatively high temperature, e.g., about 800°C to about 900°C. In some embodiments, the desired organic composition can be dissolved in a suitable solvent, such as water and / or a volatile organic solvent, for combination with the silicon-based component. This dispersion can be thoroughly mixed with the silicon-based composition. After drying the mixture to remove the solvent, the dried mixture with the silicon-based material coated with the carbon precursor can be heated in an oxygen-free atmosphere to thermally decompose the organic composition, such as an organic polymer or some low-molecular-weight solid organic composition, thereby forming a carbon coating.

[0083] Similar to silicon, oxygen-deficient silicon oxide, such as silicon dioxide (SiO₂), is also available. xThe range (0.1 ≤ x ≤ 1.9) allows for intercalation / alloying with lithium, enabling oxygen-deficient silicon oxide to function as an active material in lithium-ion batteries. These oxygen-deficient silicon oxide materials are generally referred to as silicon oxide-based materials and, in some embodiments, can contain varying amounts of silicon, silicon oxide, and silicon dioxide. Oxygen-deficient silicon oxide can incorporate relatively large amounts of lithium, allowing the material to exhibit a high specific capacity. However, silicon oxide is generally observed to have a capacity that degrades rapidly with battery cycling, similar to that observed with respect to elemental silicon.

[0084] Silicon oxide-based compositions can be formed into composite materials having high capacity and very good cycling properties, as described in the '228 patent' referenced above. In particular, oxygen-deficient silicon oxide can be formed into composites with conductive materials such as conductive carbon or metal powders, which surprisingly provide high specific capacity values ​​while significantly improving cycling. Furthermore, the performance of the material can be further improved by grinding silicon oxide into smaller particles, such as submicron structured materials. do It is possible.

[0085] In general, a wide range of composite materials are available, which may include silicon dioxide, carbon components such as graphite particles (Gr), inert metal powders (M), elemental silicon (Si), especially nanoparticles, pyrolysis carbon coatings (HC), carbon nanofibers (CNF), or combinations thereof. The component structure may or may not correspond to the structure of the components within the composite material. Thus, the general composition of a composite material can be expressed as αSiO-βGr-χHC-δM-εCNF-φSi (wherein α, β, χ, δ, ε, and φ are relative weights that can be selected such that α+β+χ+δ+ε+φ=1). Generally, 0.35<α<1, 0≦β<0.6, 0≦χ<0.65, 0≦δ<0.65, 0≦ε<0.65, and 0≦φ<0.65. Certain subsets of these composite material ranges are of particular interest. In some embodiments, a composite material of SiO and one or more carbon-based components is preferred, which can be represented by the formula αSiO-βGr-χHC-εCNF (wherein 0.35<α<0.9, 0≦β<0.6, 0≦χ<0.65 and 0≦ε<0.65 (δ=0 and φ=0), in a further embodiment 0.35<α<0.8, 0.1≦β<0.6, 0.0≦χ<0.55 and 0≦ε<0.55, in some embodiments 0.35<α<0.8, 0≦β<0.45, 0.0≦χ<0.55 and 0.1≦ε<0.65, and in an additional embodiment 0.35<α<0.8, 0≦β<0.55, 0.1≦χ<0.65 and 0≦ε<0.55). In additional or alternative embodiments, a composite material can be formed of SiO, an inert metal powder, and optionally one or more conductive carbon components, which can be represented by the formula αSiO-βGr-χHC-δM-εCNF (wherein 0.35 < α < 1, 0 ≤ β < 0.55, 0 ≤ χ < 0.55, 0.1 ≤ δ < 0.65, and 0 ≤ ε < 0.55).In further additional or alternative embodiments, composites can be formed of SiO, elemental silicon, and optionally one or more conductive carbon components, which can be represented by the formula αSiO-βGr-χHC-εCNF-φSi (wherein 0.35<α<1, 0≦β<0.55, 0≦χ<0.55, 0≦ε<0.55, and 0.1≦φ<0.65, and in further embodiments, 0.35<α<1, 0≦β<0.45, 0.1≦χ<0.55, 0≦ε<0.45, and 0.1≦φ<0.55). Those skilled in the art will recognize that any additional ranges beyond the express range described above are conceivable and within the scope of this disclosure. As used herein, the term "composite" means the application of a significant binding force, such as HEMM grinding, to closely associate the materials, as opposed to a simple blend that would not be considered to form a composite.

[0086] Various Si-SiO x - An approach based on a solution for the synthesis of CM (M=metal) composites is described in U.S. Patent Application Publication 2014 / 0308585 to Han et al., entitled "Silicon-Based Active Materials for Lithium Ion Batteries and Synthesis With Solution Processing," which is incorporated herein by reference. A silicon-based carbon composite using graphene sheets is described in U.S. Patent Application Publication 2014 / 0370387 to Angucamy et al., entitled "Silicon-Silicon Oxide-Carbon Composites For Lithium Battery Electrodes and Methods for Forming the Composites," which is incorporated herein by reference. SiO x -Si-C or SiO x -A commercially available material believed to contain Si composite material is used in the battery of the example.

[0087] The anode capacity significantly affects the energy density of the battery. The higher the specific capacity of the anode material, the lower the anode weight in a cell of the same output. When the negative electrode is manufactured from a silicon-based material, the electrode can have a discharge specific capacity of approximately 800 mAh / g to 2500 mAh / g at a C / 3 discharge of 1.5 V to 5 mV relative to lithium metal, approximately 900 mAh / g to approximately 2300 mAh / g in a further embodiment, and approximately 950 mAh / g to approximately 2200 mAh / g in another embodiment. Those skilled in the art will recognize that an additional range of discharge specific capacities within the above express range is conceivable and is within the scope of this disclosure.

[0088] positive electrode Using the improved negative electrode described above, various positive electrode chemical properties can be effectively introduced. Selected compositions can be blended into the positive electrode together with appropriate binders and conductive materials. This section focuses on positive electrode active materials particularly desirable for high-voltage cycling and moderately high capacity. This section also describes the overall electrode composition and properties.

[0089] The desired application of the final cell may, to some extent, influence the selection of the cathode composition. From this perspective, a wide range of compositions are described below. For automotive and similar applications, certain cathode chemical properties have been found desirable in terms of achieving high energy density along with cycling beyond 600 cycles while maintaining at least 80% capacity, although some materials yield promising results with somewhat lower cycling stability. In particular, nickel-rich lithium nickel-manganese-cobalt oxide provides very long cycling performance based on the improved electrolyte described herein. In another embodiment, desirable cathode performance is provided by blending nickel-rich lithium nickel-manganese-cobalt oxide with a blend of (lithium + manganese)-rich lithium nickel-manganese-cobalt oxide. Furthermore, nickel-rich lithium nickel-manganese-cobalt oxide, alone as an active material or in combination with the silicon-based anode described herein, can provide desirable high energy density with an average discharge voltage having good cycling. Examples relating to nickel-rich lithium nickel-manganese-cobalt oxide alone are shown below.

[0090] Nickel-rich lithium nickel manganese cobalt oxide (N-NMC) can provide desirable cycling and capacity characteristics for lithium-ion batteries described herein. In particular, nickel-rich compositions are of the formula LiNi x Mn y Co zThe composition can be broadly represented by O2 (wherein x+y+z≈1, 0.45≦x, 0.025≦y, z≦0.35, and in further embodiments 0.50≦x, 0.03≦y, z≦0.325, and 0.55≦x, 0.04≦y, z≦0.3). The amount of nickel can affect the selected charging voltage to balance cycling stability and discharge energy density. For values ​​of x in the range of 0.525≦x≦0.7, the selected charging voltage may be 4.25V~4.375V. For values ​​of x in the range of 0.7≦x≦0.9, the selected charging voltage may be 4.05V~4.325V. Those skilled in the art will recognize that compositions within the above express ranges and additional ranges of selected charging voltages are conceivable and within the scope of this disclosure. These compositions have been found to provide relatively stable higher voltage cycling, good capacitance, and desirable impedance. N-NMC powders can be synthesized using techniques such as the coprecipitation method, which are further described below, and are commercially available from, for example, BASF (Germany), TODA (Japan), L&F Materials Corp. (Korea), Umicore (Belgium), and Jinhe Materials Corp. (China).

[0091] With respect to N-NMC compositions, the average voltage tends to increase slightly as the nickel content increases, but the charging voltage for stable cycling tends to decrease slightly as the nickel content increases. Therefore, N-NMC active materials can provide good cycling and adequately high capacity and energy density, but the selection of active materials may come with sacrifices.

[0092] As described above, the desired blend may include N-NMC and (lithium-rich + manganese-rich) lithium nickel manganese cobalt oxide (LM-NMC or HCMR®). These compositions are of the formula Li 1+b Ni α Mn β Co γ A δ O2-z F z (wherein b+α+β+γ+δ≈1, b is in the range of about 0.04 to about 0.3, α is in the range of 0 to about 0.4, β is in the range of about 0.2 to about 0.65, γ is in the range of 0 to about 0.46, δ is in the range of about 0 to about 0.15, and z is in the range of 0 to 0.2, however both α and γ are not 0, and A is a different metal from lithium, manganese, nickel and cobalt) can be roughly represented by. In some embodiments, A may be Mg, Sr, Ba, Cd, Zn, Al, Ga, B, Zr, Ti, Ca, Ce, Y, Nb, Cr, Fe, V or a combination thereof. Also, in additional or alternative embodiments, Li 1+b Ni α Mn β Co γ A δ O2 (wherein 0.05 ≤ b ≤ 0.125, 0.225 ≤ α ≤ 0.35, 0.35 ≤ β ≤ 0.45, 0.15 ≤ γ ≤ 0.3, 0 ≤ δ ≤ 0.05) and up to 5 mole percent of oxygen can be replaced with a fluorine dopant. Those skilled in the art will recognize that additional ranges of compositions within the express range described above are conceivable and are within the disclosure. Long-term cycling stability has been achieved at relatively high cycling voltages for (lithium + manganese) rich NMC active materials, as described in U.S. Patent No. 8,928,286 to Amiruddin et al., entitled "Very Long Cycling of Lithium Batteries With Lithium Rich Cathode Materials," which is incorporated herein by reference.

[0093] The LM-NMC cathode material is coprecipitation and as detailed in the '160 patent and the '873 patent. ZoIt can be conveniently synthesized by the Lugel process. In some embodiments, the cathode material is synthesized by precipitating a mixed metal hydroxide or carbonate composition from a solution containing a +2 cation having a selected composition. The metal hydroxide or carbonate precipitate is then subjected to one or more heat treatments to form a crystalline layered lithium metal oxide composition. The carbonate coprecipitation process described in the '873 patent yielded a desirable lithium-rich metal oxide material having cobalt in its composition and exhibiting high specific capacity performance with excellent tap density. These patents also describe the effective use of metal fluoride coatings to improve performance and cycling.

[0094] With respect to LM-NMC cathode active materials, it has been found that the performance of the corresponding cells can be improved by coating the material. Suitable coating materials that are generally considered electrochemically inert during battery cycling may include metal fluorides, metal oxides, or non-fluoride halides of metals. The results of the following LM-NMC examples are obtained with LM-NMC materials coated with metal fluorides. Improved metal fluoride coatings with appropriately designed thicknesses are described in U.S. Patent No. 9,843,041, published to Lopez et al., entitled "Coated Positive Electrode Materials for Lithium Ion Batteries," which is incorporated herein by reference. Suitable metal oxide coatings are further described, for example, in U.S. Patent No. 8,535,832B2, published to Karthikeyan et al., entitled "Metal Oxide Coated Positive Electrode Materials for Lithium-Based Batteries," which is incorporated herein by reference. The discovery of non-fluoride metal halides as desirable coatings for cathode active materials is described in U.S. Patent No. 8,663,849B2 to Venkatachalam et al., entitled "Metal Halide Coatings on Lithium Ion Battery Positive Electrode Materials and Corresponding Batteries," which is incorporated herein by reference.

[0095] Regarding the active material blend for the cathode, the active material may include about 3% to about 85% by weight of LM-NMC, about 5% to about 75% by weight of LM-NMC in a further embodiment, about 6% to about 70% by weight of LM-NMC in an additional embodiment, and about 7% to about 65% by weight of LM-NMC in other embodiments. Similarly, in the cathode active material blend, the active material may include about 15% to about 97% by weight of N-NMC, about 25% to about 95% by weight in a further embodiment, about 30% to about 94% by weight in an additional embodiment, and about 35% to about 93% by weight of N-NMC in other embodiments. The cathode active material may optionally include 0 to 25% by weight of lithium cobalt oxide, LiNi 0.33 Mn 0.33 Co 0.33 O2 (NMC111), LiNi 0.8 Co 0.15 Al 0.05 Additional active materials such as O2(NCA) and mixtures thereof may be included. Those skilled in the art will recognize that an additional range of compositional blends within the express range described above is conceivable and is within the scope of this disclosure.

[0096] As described above, the positive electrode generally contains an active material and a conductive substance within the binder. The amount of active material loaded in the electrode can be large. In some embodiments, the positive electrode contains about 85 to about 99% positive electrode active material, in other embodiments about 90 to about 98% positive electrode active material, and in further embodiments about 95 to about 97.5% positive electrode active material. In some embodiments, the positive electrode has about 0.75 to about 10% polymer binder, in other embodiments about 0.8 to about 7.5% polymer binder, and in further embodiments about 0.9 to about 5% polymer binder. Generally, the positive electrode composition may also contain conductive additives different from the electroactive composition. In some embodiments, the positive electrode may have 0.4% to about 12% by weight of conductive additives, in further embodiments about 0.45% to about 7% by weight of conductive additives, and in other embodiments about 0.5% to about 5% by weight of conductive additives. Those skilled in the art will recognize that an additional range of particle loading amounts within the express range described above is conceivable and is within the scope of this disclosure. The active material for the cathode is described above. Suitable polymer binders for the cathode include, for example, polyvinylidene fluoride, polyethylene oxide, polyimide, polyethylene, polypropylene, polytetrafluoroethylene, polyacrylate, rubber, e.g., ethylene-propylene-diene monomer (EPDM) rubber or styrene-butadiene rubber (SBR), copolymers thereof, or mixtures thereof. With respect to the cathode, polyvinylidene fluoride (PVDF) can be used with good results, and the cathode in the examples uses a PVDF binder. Conductive additives are described in detail with respect to the anode, and nanoscale conductive carbon can be effectively used with respect to the cathode.

[0097] For a given loading level, the electrode density (of the active material) is inversely proportional to the thickness; therefore, electrodes with higher density will be thinner than electrodes with lower density. The loading amount is equal to the product of density and thickness. In some embodiments, the positive electrode of the battery has a load of approximately 10 to 40 mg / cm³. 2 In other embodiments, approximately 12 mg / cm³ 2~Approx. 37.5mg / cm 2 In an additional embodiment, approximately 13 mg / cm³ 2 ~about 35mg / cm 2 In other embodiments, 20 mg / cm³ 2 ~Approx. 32.5mg / cm 2 The positive electrode has a positive electrode active material loading level. In some embodiments, the positive electrode of the battery has an active material density of about 2.5 g / cc to about 4.6 g / cc in some embodiments, about 3.0 g / cc to about 4.4 g / cc in other embodiments, and about 3.25 g / cc to about 4.3 g / cc in additional embodiments. In further embodiments, the positive electrode may have a positive electrode material thickness of about 45 microns to about 300 microns on each side of the current collector after compression and drying, about 80 microns to about 275 microns in some embodiments, and about 90 microns to about 250 microns in additional embodiments. Those skilled in the art will recognize that additional ranges of active material loading levels, electrode thicknesses and electrode densities within the express ranges described above are conceivable and within the scope of this disclosure.

[0098] Complementary lithium The improved high-energy battery designs described herein generally include supplemental lithium, and this section relates to approaches for incorporating supplemental lithium for suitable embodiments. Generally, with respect to cells using silicon-based negative electrode active materials, the incorporation of supplemental lithium is desirable because the material exhibits relatively high irreversible capacity loss during the initial charging of the battery. Furthermore, supplemental lithium surprisingly stabilizes the cycling of LM-NMC. Various approaches can be used to introduce supplemental lithium into the battery, but after the corresponding initial reaction and / or charging, the negative electrode associates with an excess amount of lithium from the supplemental lithium for cycling. With respect to the negative electrode in a battery with supplemental lithium, the structure and / or composition of the negative electrode may change after the first cycle and after additional cycles compared to its initial structure and composition.

[0099] Depending on the approach to introducing complementary lithium, the positive electrode may initially include a source of complementary lithium and / or introduce a sacrificial electrode containing complementary lithium. Additionally or alternatively, complementary lithium can be associated with the negative electrode. In some embodiments, complementary lithium can be introduced to the negative electrode using electrochemical methods, as opposed to purely chemical or mechanical methods. If complementary lithium is initially placed in the positive electrode or another electrode, the negative electrode may be in an invariant form where lithium is absent until the battery is charged or, at least, until the circuit between the negative electrode and the electrode containing complementary lithium is closed in the presence of an electrolyte and separator. For example, the positive electrode or complementary electrode may include elemental lithium, lithium alloys, and / or other sacrificial lithium sources, in addition to other electrode components.

[0100] If the positive electrode contains sacrificial lithium, the lithium from the sacrificial lithium source is loaded into the negative electrode during the charging reaction. The voltage during charging based on a sacrificial lithium source can differ significantly from that when charging is performed based on the positive electrode active material. For example, elemental lithium in the positive electrode can charge the negative electrode active material without applying an external voltage, as long as the circuit is closed, the reaction can proceed by oxidation of elemental lithium. With respect to some sacrificial lithium source materials, an external voltage is applied to oxidize the sacrificial lithium source in the positive electrode and allow lithium to proceed into the negative electrode active material. Charging can generally be performed using constant current, stepwise constant voltage charging, or other convenient charging schemes. However, at the end of the charging process, the battery should be charged to the desired voltage, which then also requires the extraction of lithium from the positive electrode active material (e.g., deintercalation and dealloying).

[0101] In further embodiments, at least a portion of the complementary lithium initially associates with the anode. For example, the complementary lithium may be in the form of a lithium alloy or other lithium source that is more electronegative than the anode active material. Elemental lithium may be in the form of thin films, lithium alloy foils, and / or powders, such as those formed by vapor deposition, sputtering, or ablation. Elemental lithium, particularly in powder form, can be coated to stabilize it for handling purposes. Commercially available lithium powders, such as those from Livent Corporation, are sold with proprietary coatings for stability. This coating generally does not alter the performance of the lithium powder for electrochemical applications. After the anode is brought into contact with the electrolyte, a reaction can occur, and the complementary lithium is transported to the anode active material. Since the electrode is internally conductive, it is not necessary to close the circuit to obtain electron flow from the reaction. During this process, a solid electrolyte interface (SEI) layer may also be formed. Thus, the complementary lithium is loaded into the anode active material, and at least a portion of it is generally consumed in the formation of the SEI layer. The complementary lithium placed at the negative electrode should be more electronegative than the negative electrode active material because, upon voltage application, it does not react with the active material and the complementary lithium source at the same electrode.

[0102] In some embodiments, complementary lithium that associates with the negative electrode can be incorporated as a powder within the negative electrode. In particular, the negative electrode may include an active negative electrode composition, a complementary lithium source in a polymer binder matrix, and conductive powder, if present. In additional or alternative embodiments, the complementary lithium is arranged along the electrode surface. For example, the negative electrode may include an active layer having the active negative electrode composition and a complementary lithium source layer on the surface of the active layer. The complementary lithium source layer may include lithium or lithium alloy foil sheets, complementary lithium powder in a polymer binder, and / or particles of complementary lithium source material arranged on the surface of the active layer. In an alternative configuration, the complementary lithium source layer is located between the active layer and the current collector. Also in some embodiments, the negative electrode may include a complementary lithium source layer on both surfaces of the active layer.

[0103] Arrangements for performing electrochemical pre-loading of lithium may include an electrode having a silicon-based active material formed on a current collector, which is placed in a container containing an electrolyte and a sheet of lithium source material in contact with the electrode. The sheet of lithium source material may include lithium foil, lithium alloy foil, or lithium source material in a polymer binder together with conductive powder, which is in direct contact with the anode to be pre-loaded with lithium so that electrons can flow between the materials to maintain electrical neutrality while each reaction is taking place. In subsequent reactions, lithium is loaded into the silicon-based active material via intercalation, alloying, etc. In alternative or additional embodiments, the anode active material may be mixed in the lithium source material for the incorporation of the electrolyte and complementary lithium before being formed into the electrode having the polymer binder, so that each material can react spontaneously in the electrolyte.

[0104] In some embodiments, a lithium source within the electrode can be assembled into a cell together with an electrode pre-loaded with lithium. A separator can be placed between each electrode. A current can be passed between the electrodes to provide controlled electrochemical pre-lithiation. Depending on the composition of the lithium source, it may or may not be necessary to apply a voltage to advance lithium deposition in the silicon-based active material. Apparatus for performing such a lithiation process may include a container holding an electrolyte and a cell containing a sacrificial electrode, which includes an electrode to be used as the negative electrode in the final battery, a current collector, a separator, and a lithium source such as lithium metal foil. The separator is located between the sacrificial electrode and the electrode made of the silicon-based active material. A convenient sacrificial electrode may include lithium foil, lithium powder embedded in a polymer, or a lithium alloy, but any electrode with extractable lithium can be used. The container for the lithiated cell may include a conventional battery housing, a beaker, or any other convenient structure. This configuration has the advantage that the degree of lithiation of the negative electrode can be measured by measuring the current. Furthermore, the negative electrode can undergo one or more cycles, and the negative electrode active material is loaded to a state close to complete loading with lithium. In this way, the SEI layer can be formed to a desired degree of control during lithium pre-loading of the negative electrode active material. Subsequently, during the preparation of the negative electrode by selected lithium pre-loading, the negative electrode is fully formed.

[0105] In general, with respect to embodiments in which complementary lithium is used, the amount of complementary lithium pre-loaded or loadable into the active composition may be at least about 2.5% of the volume, about 3% to about 55% of the volume in further embodiments, about 5% to about 52.5% of the volume in additional embodiments, and about 5% to about 50% of the volume of the negative electrode active material in some embodiments. The complementary lithium may be selected to roughly adjust the balance of the IRCL of the negative electrode, but other amounts of complementary lithium may also be used as needed. In some embodiments, the amount of complementary lithium added is such that it has an oxidation capacity corresponding to 60% to 180% of the first cycle IRCL of the negative electrode, in further embodiments this is 80% to 165%, and in other embodiments it is 90% to 155%. Those skilled in the art will recognize that additional percentage ranges within the above express ranges are conceivable and are within the disclosure. Therefore, the addition of complementary lithium can effectively reduce or eliminate the contribution of the negative electrode to the IRCL, such that the measured IRCL of the battery represents a partial or majority contribution from the positive electrode's IRCL that is not reduced by the presence of complementary lithium. Those skilled in the art will recognize that the additional range of IRCL within the express range described above is conceivable and is within the scope of this disclosure.

[0106] Cathode and anode balance It has been found that the overall performance of a battery depends on the capacities of both the negative and positive electrodes, as well as their relative balance. Electrode balance has been found to be particularly important in achieving high energy density and good cycling characteristics for batteries. In some embodiments, sacrifices may be made in achieving longer cycling stability and energy density. To achieve longer cycling stability, it is desirable to balance the battery to achieve a relatively low energy density, but it may be desirable to use a battery that is suitable for stable long-term use across a wider range of operating parameters. With properly selected active materials, desired electrode design, and improved electrolyte formulations, high energy density is still achievable while achieving more than 800 cycling cycles with a capacity degradation of 80% or less. Electrode balance can be evaluated in several different ways, which can work effectively when specific evaluation approaches are appropriately considered.

[0107] Testing of active materials is performed in lithium cells using lithium metal electrodes. Such cells are commonly called half-cells, in contrast to lithium-ion cells (called full cells) in which both electrodes contain lithium alloy or intercalation material. In half-cells using silicon-based electrodes, the lithium electrode functions as the negative electrode, and the silicon-based electrode functions as the positive electrode. This is the opposite of its usual role as the negative electrode in lithium-ion cells.

[0108] The capacity of the positive electrode active material can be estimated from the capacity of the material, which can be measured by cycling the material against a lithium metal foil. For example, with respect to a given positive electrode, the capacity can be evaluated by determining the insertion capacity and extraction capacity during the first charge / discharge cycle. In this case, lithium is deintercalated or extracted from the positive electrode to a voltage selected based on material chemistry and a selected charging voltage (generally 4.2V to 4.5V) of the cell design, and then intercalated or inserted back into the positive electrode at a rate of C / 20 to 2V with slight fine-tuning, e.g., generally 0.1V, up to a higher charging voltage against the lithium metal, based on the final anode voltage against the lithium metal. Similarly, with respect to a given silicon-based electrode, the insertion capacity and extraction capacity can be evaluated using a battery having a positive electrode containing a silicon-based active material and a lithium foil negative electrode. This capacity is evaluated by determining the insertion and extraction capacities of the battery between first charge / discharge cycles, where lithium is intercalated / alloyed to a silicon-based electrode up to 5mV and deintercalated / dealloyed to 1.5V at a rate of C / 20. In actual use, the observed capacity may vary from the tested capacity due to various factors such as high-rate operation and changes in voltage range, which may be due to the battery design and the composition of the counter electrode, which is not lithium metal. With respect to some evaluation approaches, electrode balance can be evaluated using the subsequent capacity after the first cycle, and it is possible to use higher discharge rates such as C / 3 or C / 10 if necessary. The use of balance after a formation cycle or several formation cycles may be desirable in that the balance is more based on conditions between battery uses.

[0109] In most commercially available carbon-based batteries, approximately 7-10% excess anode is used compared to the cathode to prevent lithium plating. One significant concern with excess anode is that it increases the cell weight and reduces the cell's energy density. Compared to graphite, which has approximately 7% IRCL in the first cycle, high-capacity silicon-based anodes can have IRCL ranging from approximately 10% to 40%. A large portion of the capacity can become inactive within the cell after the first charge-discharge cycle, potentially adding significant dead weight to the battery.

[0110] For high-capacity anode materials, the irreversible capacity loss of the negative electrode is generally greater than that of the positive electrode, resulting in the availability of additional lithium for the cell. If the negative electrode has significantly higher irreversible capacity loss than the positive electrode, the initial charging of the negative electrode irreversibly consumes lithium, so during subsequent discharge, the negative electrode cannot supply enough lithium to the positive electrode to satisfy its full lithium-accepting capacity. This results in wasted positive electrode capacity and, correspondingly, an increase in weight that does not contribute to cycling. Most or all of the lithium loss from the net IRCL (negative IRCL - positive IRCL) can be compensated for by complementary lithium as described above. The evaluation of electrode balance between the first formation cycles may or may not take complementary lithium into account. Any excess complementary lithium that is not consumed with respect to IRCL in the formation cycle or subsequent cycles several cycles later is generally alloyed with the anode material. Electrode balance can be evaluated in post-formation cycling stages, such as the fourth cycle at a selected rate, and these capacities can be estimated from electrode performance.

[0111] From the perspective of providing stable, longer-term cycling performance, it may be desirable to balance the electrodes to effectively utilize both electrode capacities and avoid plating of the lithium metal between cycling cycles. Generally, electrode balance is considered during electrode assembly, referring to the initial electrode capacity relative to the lithium metal.

[0112] Generally, battery life can be selected to terminate when energy output drops by approximately 20% from the initial capacity at a constant discharge rate, although other values ​​can be selected as needed. With respect to the materials described herein, the capacity degradation due to negative electrode cycling is generally greater than that of the positive electrode; therefore, avoiding lithium metal deposition due to cycling suggests a higher negative electrode excess capacity to further stabilize cycling. Generally, if the negative electrode capacity degrades at approximately twice the rate of the positive electrode capacity, it is desirable to include at least 10% additional negative electrode capacity to accommodate cycling. In robust battery designs, at least approximately 10% additional negative electrode capacity may be desirable under various discharge conditions. Generally, the initial negative electrode charge capacity, evaluated at a C / 20 rate from the open-circuit voltage up to 1.5V for lithium, can be balanced to approximately 110–195%, in a further embodiment approximately 120–185%, and in an additional embodiment approximately 130–190%, relative to the sum of the initial positive electrode charge capacity plus the oxidation capacity of any complementary lithium at a C / 20 rate from the open-circuit voltage up to the cell design charge voltage (generally 4.2V–4.6V). Alternatively, the electrode balance can be evaluated at a discharge rate of C / 10 or C / 3 in the fourth cycle with a negative electrode capacity of approximately 110–195%, in a further embodiment approximately 120–185%, and in an additional embodiment approximately 130–190% for positive electrode capacity. Those skilled in the art will recognize that additional ranges of balance within the express range described above are conceivable and within the scope of this disclosure. Such balances are described in the battery designs described below.

[0113] Performance characteristics The improved electrolyte formulations described herein can further extend the cycling improvements obtained by negative electrode designs, which are particularly effective with respect to silicon-based materials. The combination of design features described herein can provide longer cycling stability while maintaining desirable battery performance. Achieving long-term cycling involves the use of the improved electrode designs described herein, which have a balance of cell design parameters in combination with improved electrolyte formulations that remarkably extend cycling with unprecedented stability.

[0114] The selected charging voltage may be affected by the positive electrode active material. Generally, the selected charging voltage for these cells is about 4.05V to 4.4V. The battery can exhibit very good cycling performance. In some embodiments, the battery can exhibit at least about 80% of its 6th cycle capacity when discharged at a rate of 1C from the selected charging voltage to 2.5V at 30°C at 700 cycles, at least about 82% of its 6th cycle discharge capacity when cycled at C from the selected charging voltage to 2.5V at 30°C at 700 cycles, and at least about 84% of its 6th cycle discharge capacity in additional embodiments. Similarly, the battery may exhibit at least about 80% of its 6th cycle capacity at 725 cycles, discharged at 30°C at a 1C rate from a selected charge voltage to 2.5V, and at 750 cycles, at 30°C at a C / 3 rate from a selected charge voltage to 2.5V, and at least about 80% of its 6th cycle discharge capacity at 750 cycles, and at 800 cycles in an additional embodiment. Comparable results are obtained at 2C charge and discharge rates. Those skilled in the art will recognize that any additional ranges beyond the express range described above are conceivable and within the scope of this disclosure. [Examples]

[0115] General methods and materials. Electrolyte formulations were tested by their incorporation into coin cells using NMC positive electrodes and negative electrodes incorporating a blend of silicon oxide-based composite and graphite as active materials. In particular, the active material of the positive electrode has the formula LiNi 0.6 Mn 0.2 Co 0.2 O2(NMC622) or commercially available lithium nickel manganese cobalt oxide having LiNi 0.8 Mn 0.1 Co 0.1 O2(NMC811). The negative electrode active material was a commercially available SiO-Si-C (SiOx) composite blended with electrochemically active graphite.

[0116] To form a negative electrode using a silicon oxide-based active material, unless otherwise specified, the active material is 65 wt% to 80 wt% of a commercially available silicon oxide / silicon / carbon composite material (herein referred to as SiO x / Si / C) powder, and the remainder (20 wt% to 35 wt%) is formed by blending graphite (KS 6 synthetic graphite, Imerys). The negative electrode active material was thoroughly mixed with 1 wt% to 7 wt% of a nanoscale carbon conductive additive to form a homogeneous powder mixture. The negative electrode had 2 to 6 wt% of carbon nanotubes as the conductive additive. The powder components of the electrode, the active material and the carbon nanotubes were mixed to form a homogeneous powder mixture. The negative electrode had 1 to 7 wt% of a lower modulus binder and 7 to 15 wt% of polyimide. The weight ratio of the lower modulus binder to polyimide was 0.714.

[0117] To form the negative electrode, a blend of polymer binder, polyimide binder, and low modulus binder was mixed with N-methylpyrrolidone ("NMP") (Sigma-Aldrich) and stirred overnight to form a polymer binder-NMP solution. A homogeneous powder mixture was then added to the polymer binder-NMP solution and mixed for approximately 2 hours to form a homogeneous slurry. The slurry was applied to a copper foil current collector to form a wet thin film, and the laminated current collector was dried in a reduced-pressure oven to remove the NMP and cure the polymer. The laminated current collector was then pressed between rollers of a sheet mill to obtain the desired laminate thickness. The dried laminate contained 2-20% by weight of binder, with the remainder of the electrode contributed by powder. The negative electrode was electrochemically pre-lithified with sufficient lithium to compensate for 100-160% of the lithium loss due to irreversible capacitance loss of the anode.

[0118] The cathode had a loading of approximately 93 to 97.5% active material, blended with 1% to 4% by weight of PVDF binder and 1% to 3% by weight of nanoscale carbon. The cathode material was blended with NMP solvent, spread onto an aluminum foil current collector, pressed, and dried.

[0119] To form the coin cell, the negative electrode portion was cut to the same size as the separator, and the positive electrode portion was also cut to the same size. The separator for these cells was a Celgard® porous polymer membrane. The electrodes with the separator between them were placed in the coin cell housing. The electrolyte selected as described below was placed in the cell, and the cell was sealed.

[0120] The assembled cells were cycled at 23°C at 4.3V to 2.5V for NMC622 cells and at 4.2V to 2.5V for NMC811 cells. The cells were charged and discharged at a rate of C / 10 in the first cycle, at a rate of C / 5 in the second cycle, and then cycled at a rate of C / 3.

[0121] Examples 8 and 9 relate to pouch cells, and the formation of these cells is further described below.

[0122] Example 1 - Cell using NMC cathode and commercially available electrolyte This embodiment demonstrates the cycling performance in a coin cell using a blend of NCM cathode active material, anode active material, and a commercially available electrolyte.

[0123] In the first combination of cells, the negative electrodes of these cells were as described in the Materials and Methods section above. The positive electrodes were LiNi as the positive electrode active material of the cells. 0.8 Mn 0.1 Co 0.1 O2 (NMC811) or LiNi 0.6 Mn 0.2 Co 0.2 The cells contained either O2 (NMC622). Cells were formed using different loading amounts of the positive electrode active material. The NMC622 cells were cycled on either 4.30V to 2.5V or 4.35V to 2.5V, and the NMC811 cells were cycled on a voltage range of 4.20V to 2.5V.

[0124] Initial charge-discharge cycles were performed at a rate of C / 10. The results for all samples are summarized in Table 1.

[0125] JPEG0007933852000003.jpg80169

[0126] Furthermore, cells corresponding to samples C1 to C8 were also cycled. Specifically, the cells were charged and discharged at a rate of C / 10 in the first cycle, at a rate of C / 5 in the second cycle, and then cycled at a rate of C / 3. Table 2 summarizes the rate capacities of the cell samples based on the discharge capacity at the specified discharge rates.

[0127] JPEG0007933852000004.jpg73165

[0128] The discharge capacity as a function of cycles for samples C2, C4, and C7 is plotted in Figure 5, and the normalized capacity as a function of cycles is plotted in Figure 6. The best cycling performance of these coin cells was achieved with the NMC622-based sample cycled from 4.30V to 2.5V, while the lowest cycling performance across the entire cycle range was achieved with the NMC622-based sample cycled from 4.35V to 2.5V.

[0129] Example 2 - Electrolyte formulation for silicon dioxide-based lithium-ion cells This embodiment provides a set of electrolyte formulations designed for silicon dioxide-based active materials to be used in combination with NMC active materials, along with their ion conductivity measurements.

[0130] Electrolyte formulations. Table 3 presents electrolyte formulations with various lithium hexafluorophosphate (LiPF6) concentrations and solvent contents. The table shows the LiPF6 concentration for each electrolyte formulation, as well as the weight percentage ranges of fluoroethylene carbonate (FEC), dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), fluorobenzene (FB), propylene carbonate (PC), 1,3-propane sulfate (PS), and ethyl carbonate (EC) (percentage values ​​are volume percentages relative to the solvent), and the conductivity measurements (25°C) for each formulation.

[0131] JPEG0007933852000005.jpg245169

[0132] Example 3 - Rate performance of electrochemical cells with selected electrolyte formulations This embodiment demonstrates the rate performance achievable with the electrolyte selected from Example 2.

[0133] The coin cells were formed as described above in Example 1, except that the electrolyte selected from Table 3 was used. Table 4 shows the relationship between electrolyte conductivity and rate performance for the five electrolyte formulations in Table 3. The assembled cells were cycled after the first two formation cycles with different charge / discharge rates, e.g., 0.333C / 0.333C, 1C / 1C, and 2C / 1C, for electrolyte formulations 1, 2, 3, 7, and 10.

[0134] JPEG0007933852000006.jpg65169

[0135] Example 4 - Electrolyte dependence on the cycling performance of NMC622 / SiOx lithium-ion cells This embodiment describes the cycling performance of coin cells based on various electrolyte formulations.

[0136] Effect of ethylene carbonate. Figures 7 (1C / 1C) and 8 (2C / 2C) show the detrimental effect on the rate performance of lithium-ion battery systems when the electrolyte formulation contains ethylene carbonate. The coin cells for this embodiment are based on the NMC622 cathode active material. The anode and coin cells were formed as described in Example 1. For example, with respect to the coin cell with electrolyte number 1 (Table 3), the rate performance of the system deteriorated significantly after the addition of ethylene carbonate to the formulation. Compared with commercially available electrolytes listed in Table 3 (products 1 and 2), formulations 1 and 2 containing 0% ethylene carbonate showed superior performance in both 1C and 2C cycling. Electrolyte 1 showed somewhat better cycling performance compared to electrolyte 2.

[0137] Effect of fluoroethylene carbonate concentration. Figures 9 and 10 show the normalized (Figure 9) and unnormalized (Figure 10) 1C charge and discharge cycling performance of coin cells containing electrolyte formulations with varying amounts of fluoroethylene carbonate from 0% to 30% by volume. This data indicates that at least 5–10% FEC additive is necessary to obtain more than 700 cycles to retain 80% of the silicon-based cell capacity. Electrolytes with 10% or 15% FEC had the best cycling performance compared to electrolytes with less or more FEC. Electrolytes without FEC had insufficient cycling performance.

[0138] Effect of Solvents. For 1C cycling applications, various amounts of dimethyl carbonate, ethyl methyl carbonate, and diethyl carbonate in the electrolyte formulation resulted in relatively consistent performance in battery cycle life, for example, 765-805 cycles at 80% capacity retention in coin cells (Figures 11 (1C / 1C) and 12 (2C / 2C)). However, the best results were obtained using at least some DMC and not too much DEC. However, for 2C cycling applications, cycling performance is affected by various solvent ratios. For example, if the electrolyte contains more than 70% DEC, cycling performance decreases. Neither high weight percentages of DMC nor EMC adversely affect cycling performance, but the best results were obtained with several blends of solvent components mixed with room-temperature liquid solvent components, i.e., FEC.

[0139] Effects of Solvents and Additives. The effects of fluorobenzene and propylene carbonate as additives were investigated. These are shown in Table 3 as Electrolytes 12-14. In all tested additive formulations, the coin cells showed consistent cycling performance, e.g., 770-780 cycles at 80% capacity (Figures 13 (normalized) and 14 (unnormalized capacity)). This result was also similar to the performance of Electrolyte 7, the closest electrolyte without additives, as shown in Figure 11.

[0140] Example 5 - Cycling performance of NMC811 / SiOx coin cell This example demonstrates the cycling performance of the NMC811 active material in the cathode / cathode for one of the electrolytes developed for silicon oxide-based negative electrode active materials.

[0141] Electrolyte 2 was also used to cycle coin cells similar to those described in Examples 1, 3, and 4, which were formulated with NMC811 positive electrode active material and SiOx negative electrode. These cells were cycled at 2.5V to 4.2V. Cycling performance is shown in Figures 15 (1C / 1C) and 16 (2C / 2C). The 1C and 2C coin cell applications provide higher cycling performance than 700 cycles to 80% capacity retention when Electrolyte 2 is used as the electrolyte. Cycling is slightly better with respect to the NMC811 electrode in the 1C / 1C case and slightly worse with respect to the NMC811 electrode in the 2C / 2C case, but the cycling performance is comparable to that of NMC622.

[0142] Example 6 - High-capacity long-term cycling battery with commercially available electrolyte This embodiment demonstrates long-term cycling stability based on an improved negative electrode loaded into a large battery.

[0143] The pouch cell was designed with a target capacity of approximately 11 Ah. The prismatic pouch cell had approximate dimensions of 145 mm × 64 mm × 7.7 mm (thickness), excluding tabs. The cell design is shown in Figures 17 and 18. Electrodes were formed as described in the materials and methods above, and the separator sheet was pleated by the plated electrodes disposed in the folds of the separator. The separator for the pouch cell was a porous polymer composite sheet with a gel-forming polymer coating. Supplemental lithium was provided by applying lithium powder (SLM®, Livent Corp.) to the negative electrode surface prior to assembly to roughly compensate for 100% to 160% of the IRCL of the silicon-based negative electrode active material. The battery was designed to have a total capacity of about 11 Ah at a discharge rate of C / 3 at 30°C. The battery was cycled through one formation cycle at a charge and discharge rate of C / 20. The cells were then cycled at 30°C at a charge rate and a discharge rate of C / 3.

[0144] With an NMC811-based positive electrode, and 75 to 90 wt% SiO x A 11 Ah cell was formed from the same anode as described above by the coin cell above, from an NMC622-based positive electrode with an anode having an active material of / Si / C composite and 10 to 25 wt% graphite. Based on the low rate (C / 20) capacity, the negative electrode capacity was initially 130% to 160% of the positive electrode capacity. The negative electrode had a blend of polyimide, a lower modulus binder, and a carbon nanotube conductive material. A commercially available fluorinated electrolyte was also used. For the cells with NMC622 positive electrodes, two comparable representative cells were cycled between 4.3 V and 2.5 V. The cycling results are plotted in Figures 19 and 20. In Figures 19 and 20, specific capacity and normalized specific capacity are plotted as a function of cycles.

[0145] For cells using an NMC811 cathode, comparable cells were cycled at a rate of C / 3 from 4.15V to 2.5V and from 4.20V to 2.5V. The cycling results are plotted in Figures 21 and 22. In Figures 21 and 22, the specific capacitance and normalized specific capacitance are plotted as a function of the cycle.

[0146] Example 7 - Cycling performance of NMC622 / SiOx pouch cells with improved electrolyte This example investigates the cycling performance of pouch cell morphology using silicon oxide-based active materials with the improved electrolyte described herein.

[0147] The cycling performance of an NMC622 / SiOx-based 11Ah 285Wh / kg pouch cell was tested using three different electrolyte formulations from Table 3. The pouch cell structure was identical to that described in Example 6, but the electrodes and novel electrolyte formulations were used as described in the Materials and Methods section. Figures 23 and 24 show plots of normalized discharge capacity (Figure 23) and unnormalized discharge capacity (Figure 24) for electrolytes 2, 7, and 10. Cells formed with electrolyte 2 provide cycling performance of more than 1000 cycles up to 80% capacity retention. For 1C pouch cell applications, this result, compared with formulations 7 and 10, indicates that electrolyte formulations containing more than 70% by weight of DMC are preferable in electrolyte formulations containing LiPF6 and FEC.

[0148] Example 8 - Blended Cathode Active Material This embodiment demonstrates the usefulness of an improved electrolyte for cycling with a cell having a cathode made of a blend of active materials.

[0149] The positive electrode was formed by a blend of nickel-rich lithium nickel manganese cobalt oxide (N-NMC) combined with lithium-manganese-rich NMC (LM-NCM). Several LM-NMC compositions were found to exhibit relatively low DC resistance while maintaining relatively high capacity and excellent cycling, as described in U.S. Patent No. 9,552,901B2 to Amiruddin et al. (hereinafter referred to as the '901 patent), entitled “Lithium Ion Batteries With High Energy Density, Excellent Cycling Capability and Low Internal Impedance,” which is incorporated herein by reference. The negative electrode was identical to that described in Example 2, and the coin cell was formed as described in Example 2.

[0150] Cycling results were obtained for cells with five different electrolytes from Table 3, particularly electrolytes 1, 2, 3, 7, and 8. The cells were cycled from 4.25V to 2.3V at a 1C / 1C charge / discharge rate after the first cycle. The cycling results are plotted in Figures 25 (normalized capacity) and 26 (unnormalized discharge capacity). Similar cycling results were obtained for all electrolytes except electrolyte 1. For all electrolytes, improved cycling was obtained compared to the uniform results obtained with commercially available fluorinated electrolytes (see application '209 above), and the results for electrolytes 2, 3, 7, and 8 were significantly better. However, the cycling results were not as good as those for N-NMC-based cathodes.

[0151] The embodiments described above are for illustrative purposes only and are not limiting. Additional embodiments are within the scope of the claims. In addition, although the present invention is described with reference to specific embodiments, those skilled in the art will recognize that variations in shape and detail may be made without departing from the spirit and scope of the invention. Any incorporation by reference to the above-mentioned documents is limited so as not to incorporate subject matter contrary to the express disclosure herein. To the extent that a particular structure, composition and / or process is described herein by components, elements, components or other classifications, it is understood that the disclosure herein, unless otherwise specifically indicated, includes embodiments that consist of specific components, components, components or other classifications, as shown in this discussion, and embodiments that consist of specific components, components or other classifications, as well as additional features that do not alter the fundamental nature of the subject matter.

Claims

1. A negative electrode comprising 75% to 92% by weight of an active material, 1% to 7% by weight of nanoscale conductive carbon, and 6% to 20% by weight of a polymer binder, wherein the active material comprises 35% to 95% by weight of a silicon dioxide-based material and 5% to 65% by weight of graphite, and the silicon dioxide-based material comprises a silicon-silicon dioxide-carbon composite material; Here, the polymer binder comprises a polyimide having a tensile strength of at least 60 MPa. Formula LiNi x Mn y Co z O 2 A positive electrode comprising lithium nickel manganese cobalt oxide, conductive carbon, and a polymer binder, represented by the equation (wherein x + y + z ≈ 1, 0.3 ≤ x, 0.025 ≤ y ≤ 0.35, and 0.025 ≤ z ≤ 0.35); A separator between the negative electrode and the positive electrode; An electrolyte comprising 1 M to 2 M lithium salt and a non-aqueous solvent, wherein the non-aqueous solvent consists of 5% to 30% by volume of fluoroethylene carbonate, ethyl methyl carbonate, and optionally one or more dimethyl carbonates, 0.5% to 12% by volume of propylene carbonate, 0.01% to 5% by volume of other solvent components, or mixtures thereof; The negative electrode, positive electrode, separator, and container surrounding the electrolyte Lithium-ion cells containing this material.

2. The lithium-ion cell according to claim 1, further comprising complementary lithium in an amount equivalent to 80% to 180% of the irreversible capacity loss of the first cycle of the negative electrode.

3. The lithium-ion cell according to claim 1 or 2, wherein the non-aqueous solvent comprises 5% to 20% by volume of fluoroethylene carbonate.

4. The lithium-ion cell according to claim 1 or 2, wherein the non-aqueous solvent comprises fluoroethylene carbonate and ethyl methyl carbonate.

5. The lithium-ion cell according to claim 1 or 2, which can be cycled at a charge rate of 1C and a discharge rate of 1C for at least 700 cycles without a capacity reduction of more than 20% with respect to the third cycle capacity.

6. The active material of the negative electrode comprises 40% to 90% by weight of a silicon dioxide-based material and 10% to 60% by weight of graphite, wherein the graphite is 2m 2 / g to 100m 2 A lithium-ion cell according to claim 1 or 2, having a BET surface area of ​​1 / g.

7. The lithium-ion cell according to claim 1 or 2, wherein the polymer binder of the negative electrode comprises a blend of polyimide and a second binder polymer selected from the group consisting of polyvinylidene fluoride, carboxymethylcellulose, styrene-butadiene rubber, lithified polyacrylic acid, copolymers thereof, and mixtures thereof, and the polyimide has an elongation of at least 50%.

8. The lithium-ion cell according to claim 7, wherein the second binder has an elastic modulus of 2 GPa or less.

9. The lithium-ion cell according to claim 7, wherein the negative electrode has 1 to 7% by weight of a binder with a lower modulus of elasticity and 7 to 15% of polyimide.

10. The lithium nickel manganese cobalt oxide is of the formula LiNi x Mn y Co z O 2 (wherein x+y+z≈1, 0.50≦x, 0.03≦y≦0.325, and 0.03≦z≦0.325), the lithium ion cell according to claim 1 or 2.

11. The lithium-ion cell according to claim 2, wherein complementary lithium is present in an amount equivalent to 80% to 180% of the irreversible capacity loss in the first cycle of the negative electrode, and in the fourth cycle at a discharge rate of C / 3, the ratio of the negative electrode capacity divided by the positive electrode capacity is 1.10 to 1.95.

Citation Information

Patent Citations

  • Electrolyte solvent for improving battery safety and lithium secondary battery containing the same

    JP2007504628A

  • Negative electrode for lithium ion secondary battery and secondary battery using the same

    JP2011048969A

  • Secondary battery and vehicle mounted with the same

    JP2013182807A

  • Mixed active material for lithium secondary battery, positive electrode for lithium secondary battery, and lithium secondary battery

    JP2016119288A

  • Lithium ion battery

    JP2016167394A